Curable composition comprising a multi-stage polymer
By using specific additives of multistage polymers and thermoplastic polymers in the (meth)acrylic resin polymerization process, curing shrinkage and cracking problems are solved, and the mechanical properties of the polymer are improved, making it suitable for a variety of applications.
Patent Information
- Application Number
- CN202080088724.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-19
- Filing Date
- 2020-12-21
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-12-21
AI Technical Summary
During the polymerization of (meth)acrylic resins, the prior art is difficult to effectively reduce curing shrinkage and prevent crack formation, resulting in high brittleness of the obtained polymer.
Curable compositions are employed that contain a multistage polymer and a specific additive of a (meth)acrylate-compatible thermoplastic polymer through which energy is absorbed and dissipated during the polymerization process, reducing curing shrinkage and preventing cracks.
It effectively reduces curing shrinkage and prevents crack formation, improves the mechanical properties of the polymer, such as Tg, Young's modulus and hardness, making it suitable for the manufacture of molded products with larger thicknesses and products containing high load fillers or reinforcement fibers.
Smart Images

Figure FDA0005306543150000021 
Figure FDA0005306543150000031 
Figure FDA0005306543150000041
Abstract
Description
Technical Field
[0001] The present invention is directed to a curable composition comprising a (meth)acrylic monomer, an ethylenically unsaturated oligomer, and a specific multi-stage polymer additive, which is used as a processing aid to reduce cure shrinkage and reduce or prevent crack formation during polymerization of the composition. Background Art
[0002] Free radical polymerization is a standard technique for rapidly obtaining hardened three-dimensional thermosetting polymer networks from ethylenically unsaturated compounds such as (meth)acrylates. During polymerization, (meth)acrylic resins change from a liquid state to a solid state. (Meth)acrylic resins increase in viscosity until they become rigid. At a certain point known as the gel point, plastic deformation can no longer compensate for stresses due to changes in density and reduction in volume of the material. This phenomenon, also known as curing shrinkage, can lead to crack formation during polymerization, especially when relatively thick layers of material are polymerized in a mold and / or when the material contains a large amount of monomers / reactive diluents, fillers and / or reinforcing fibers. The resulting polymer is therefore brittle and exhibits interfacial adhesion losses, for example, on the mold surface and / or around fillers or reinforcing fibers.
[0003] Artificial marble and artificial stone in the form of slabs or blocks are generally composed of mineral fillers dispersed in a polymeric matrix. Polyester or styrenic resins are generally used as the polymeric matrix. Unfortunately, when polyester resins are used, the resulting products show poor aging resistance, especially under outdoor conditions, because they are sensitive to ultraviolet radiation.
[0004] (Meth)acrylic resins represent an attractive alternative to polyester resins as they exhibit excellent aging resistance. However, due to the thickness of the slabs or blocks and the high concentration of mineral fillers, artificial marble and artificial stone based on (meth)acrylates are particularly prone to cure shrinkage and crack formation during polymerization.
[0005] It would therefore be desirable to find an additive that reduces cure shrinkage and reduces or prevents crack formation during polymerization of (meth)acrylic resins. The resulting resin would thus have excellent mechanical properties (Tg, Young's modulus, hardness) and be useful in a variety of applications, in particular for obtaining thick molded articles and / or articles containing high loads of fillers or reinforcing fibers, such as artificial marble, artificial stone, sealants, adhesives, and composites.
[0006] The present inventors have found that specific additives based on a combination of a multistage polymer and a thermoplastic polymer compatible with (meth)acrylates are able to absorb and dissipate part of the energy released during the polymerization of (meth)acrylic resins and thus reduce cure shrinkage and reduce or prevent crack formation. Summary of the invention
[0007] A first subject of the present invention is a curable composition comprising:
[0008] i) a composition (P1), said composition (P1) comprising:
[0009] - a monomer (M1) comprising at least one (meth)acrylate group and at least one functional group selected from (meth)acrylate, hydroxyl, silane, ketone, and epoxy, the monomer (M1) having a weight average molecular weight (Mw) of 100 to 420 g / mol, in particular 120 to 400 g / mol;
[0010] - an oligomer (O1) comprising at least 2 ethylenic unsaturations, preferably 2 to 10 ethylenic unsaturations, said oligomer (O1) having a weight average molecular weight (Mw) of 421 to 10 000 g / mol, in particular 450 to 3000 g / mol;
[0011] - an additive (AD), said additive (AD) comprising:
[0012] a) a multistage polymer (MP1), said multistage polymer (MP1) comprising
[0013] a1) one grade (SA1) comprising a polymer (A1) having a glass transition temperature of less than 10°C; and
[0014] a2) one stage (SA2) comprising a polymer (A2) having a glass transition temperature of at least 60°C; and
[0015] b) a thermoplastic polymer (B1 ) having a glass transition temperature of at least 30°C; and
[0016] ii) a composition (P2), said composition (P2) comprising a free radical initiator.
[0017] The present invention also relates to a process comprising polymerizing the curable composition according to the invention.
[0018] Another subject of the invention is an article obtained by polymerizing the curable composition according to the invention. In particular, the article may be a molded article, a composite, an adhesive, a chemical anchoring system, a sealant, a dental filling, or an electrical insulation coating, more particularly an artificial marble or an artificial stone.
[0019] Another aspect of the present invention is the use of the curable composition according to the present invention for preparing molded articles, composites, adhesives, chemical anchoring systems, sealants, dental fillings, or electrical insulating coatings. In particular, the curable composition can be used to prepare artificial marble or artificial stone.
[0020] The present invention also relates to the use of an additive in a curable composition for reducing cure shrinkage and reducing or preventing crack formation during polymerization of the composition, the additive being an additive (AD), the additive (AD) comprising:
[0021] a) a multistage polymer (MP1), said multistage polymer (MP1) comprising:
[0022] a1) one grade (SA1) comprising a polymer (A1) having a glass transition temperature of less than 10°C; and
[0023] a2) one stage (SA2) comprising a polymer (A2) having a glass transition temperature of at least 60°C; and
[0024] b) A thermoplastic polymer (B1 ) having a glass transition temperature of at least 30°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Showing photos of each sample in Example 3;
[0026] Figure 2 The gelation time (Tgel, in minutes) and the exothermic peak (TEP, in °C) of each sample in Example 3 are shown; and
[0027] Figure 3 Photos of each sample in Example 5 are shown. DETAILED DESCRIPTION
[0028] Composition
[0029] The curable composition of the present invention comprises composition (P1) and composition (P2). It may further optionally comprise composition (P3) and / or composition (P4).
[0030] Composition (P1)
[0031] The composition (P1) comprises a monomer (M1), an oligomer (O1), and an additive (AD). In one embodiment, the composition (P1) consists essentially of the monomer (M1), the oligomer (O1), the additive (AD) and optionally an activator.
[0032] Monomers (M1) and oligomers (O1) account for the major part of the composition (P1). In one embodiment, the total weight of monomers (M1) and oligomers (O1) accounts for 87 to 99%, particularly 90 to 98.5%, more particularly 92 to 97.5%, even more particularly 94 to 96.5% of the weight of the composition (P1).
[0033] Monomers (M1) and oligomers (O1) contain polymerizable carbon-carbon double bonds. As used herein, the term "polymerizable carbon-carbon double bond" is a carbon-carbon double bond that can react with another carbon-carbon double bond in a polymerization reaction. Polymerizable carbon-carbon double bonds are generally contained in (meth)acrylate groups or vinyl groups (-CH=CH2). As used herein, the term "(meth)acrylate group" encompasses acrylate groups (-O-CO-CH=CH2) and methacrylate groups (-O-CO-C(CH3)=CH2). The carbon-carbon double bonds of benzene rings are not considered to be polymerizable carbon-carbon double bonds.
[0034] In one embodiment, the weight ratio between the oligomer (O1) and the monomer (M1) may be 20 / 80 to 80 / 20, particularly 25 / 75 to 75 / 25, more particularly 30 / 70 to 70 / 30. Increasing the amount of the monomer (M1) in the composition (P1) may result in the introduction of short chains and an increase in the content of polymerizable carbon-carbon double bonds. The network density is thus increased, and the resulting composition is more prone to internal stress and curing shrinkage.
[0035] In a preferred embodiment, the weight ratio between the oligomer (O1) and the monomer (M1) may be 20 / 80 to 50 / 50, specifically 25 / 75 to 45 / 55, more specifically 30 / 70 to 40 / 60.
[0036] In another embodiment, the weight ratio between the oligomer (O1) and the monomer (M1) may be 45 / 55 to 75 / 25, specifically 50 / 50 to 70 / 30, more specifically 55 / 45 to 65 / 35.
[0037] The weight ratio between the oligomer (O1) and the monomer (M1) can be adjusted so that the resulting mixture has a sufficient concentration of polymerizable carbon-carbon double bonds. For example, the mixture of the monomer (M1) and the oligomer (O1) can have a polymerizable carbon-carbon double bond content (%C=C 混合物), based on the weight of the monomer (M1) and the oligomer (O1).
[0038] The %C=C 混合物 It can be determined by the following equation:
[0039] %C=C 混合物 =(w 低聚物 ×%C=C 低聚物 )+(w 单体 ×%C=C 单体 )
[0040] in
[0041] w 低聚物 is the weight % of oligomer (O1), based on the total weight of monomer (M1) and oligomer (O1);
[0042] %C=C 低聚物 is the polymerizable carbon-carbon double bond content of oligomer (O1) as defined below in the oligomer (O1) section;
[0043] w 单体 is the weight % of monomer (M1), based on the total weight of monomer (M1) and oligomer (O1); and
[0044] %C=C 单体 is the polymerizable carbon-carbon double bond content of monomer (M1) as defined below in the monomer (M1) section.
[0045] Advantageously, the additive (AD) can be used as a processing aid to reduce the cure shrinkage and reduce or prevent crack formation during the polymerization of the composition. Advantageously, the amount of additive (AD) is kept low to avoid increasing the viscosity of the composition (P1) and changing the mechanical properties of the polymerized product. In particular, the amount of additive (AD) in the composition (P1) may be 1 to 15%, particularly 2 to 10%, more particularly 3 to 8%, even more particularly 4 to 6%, based on the total weight of the monomer (M1) and the oligomer (O1).
[0046] Advantageously, the composition (P1 ) exhibits a viscosity at 25°C ranging from 200 to 1000 mPa.s, particularly from 300 to 900 mPa.s, more particularly from 400 to 800 mPa.s.
[0047] In one embodiment, the composition (P1) comprises:
[0048] - 15 to 80%, in particular 20 to 75%, more particularly 25 to 70%, of monomers (M1);
[0049] - 15 to 80%, in particular 20 to 75%, more particularly 25 to 70%, of oligomers (O1); and
[0050] - 1 to 13%, in particular 1.5 to 10%, more particularly 2.5 to 8%, even more particularly 3.5 to 6% of additives (AD);
[0051] % are % by weight, based on the weight of composition (P1).
[0052] Monomer (M1)
[0053] The composition (P1) comprises a monomer (M1). The composition (P1) may comprise a mixture of a plurality of monomers (M1).
[0054] The monomer (M1) comprises at least one (meth)acrylate group and at least one functional group selected from (meth)acrylate, hydroxyl, silane, ketone and epoxy.
[0055] The monomer (M1) may contain at least 2, preferably 2 to 4, more preferably 2 or 3 (meth)acrylate groups. In particular, the monomer (M1) may contain at least 2, preferably 2 to 4, more preferably 2 or 3 methacrylate groups.
[0056] Monomer (M1) may contain at least one (meth)acrylate group and at least one functional group selected from hydroxyl, silane, ketone, and epoxy, in particular at least one functional group that is a hydroxyl group. In particular, monomer (M1) may contain at least one methacrylate group and at least one functional group that is a hydroxyl group.
[0057] Preferably, the monomer (M1) is selected so as to have a moderate concentration of (meth)acrylate groups. For example, the monomer (M1) may have a polymerizable carbon-carbon double bond content (%C=C 单体 ), based on the weight of monomer (M1).
[0058] %C=C 单体 It can be determined according to the following formula:
[0059]
[0060] in
[0061] f 单体 is the number of (meth)acrylate groups of monomer (M1); and
[0062] M 单体 is the weight average molecular weight of the monomer (M1).
[0063] The monomer (M1) has a weight average molecular weight (Mw) of 100 to 420 g / mol, particularly 120 to 400 g / mol, more particularly 140 to 350 g / mol. The monomer (M1) may have a weight average molecular weight (Mw) of 100 to 420 g / mol, particularly 200 to 400 g / mol, more particularly 230 to 350 g / mol. Alternatively, the monomer (M1) may have a weight average molecular weight (Mw) of 100 to 420 g / mol, particularly 120 to 300 g / mol, more particularly 140 to 250 g / mol.
[0064] The monomer (M1) may exhibit a dynamic viscosity at 23° C. of 3 to 400 mPa.s, specifically 4 to 150 mPa.s, more specifically 5 to 50 mPa.s, even more specifically 6 to 20 mPa.s.
[0065] Monomer (M1) may exhibit a Tg of -10 to 100°C, specifically 10 to 90°C, more specifically 20 to 80°C.
[0066] Monomer (M1) can be a (meth) acrylate of a polyol, wherein some or all of the hydroxyl groups of the polyol are (meth) acrylated. When all hydroxyl groups are (meth) acrylated, monomer (M1) comprises two or more (meth) acrylate groups. When only some of the hydroxyl groups are (meth) acrylated, monomer (M1) comprises one or more (meth) acrylate groups and one or more hydroxyl groups. Monomer (M1) can be selected from (meth) acrylated polyols (polyols) and (meth) acrylated alkoxylated polyols. These monomers can be the reaction product of (meth) acrylic acid and a polyol. Esterification can be performed so that a significant concentration of residual hydroxyl groups remain in the polyol, or esterification can be performed so that all or substantially all of the hydroxyl groups of the polyol have been (meth) acrylated. Methacrylated polyols and methacrylated alkoxylated polyols are particularly preferred. The polyol can be aliphatic, alicyclic (it includes one or more alicyclic rings), or can contain one or more aromatic rings (such as in the case of phenols or bisphenol A). By "alkoxylated" is meant that the base polyol has been reacted with one or more epoxides (such as ethylene oxide and / or propylene oxide) to introduce one or more ether moieties (e.g., -CH2CH2-O- and / or -CH2-CH(CH3)-O-) onto the hydroxyl groups of the polyol prior to esterification to introduce one or more (meth)acrylate functional groups. For example, the amount of epoxide reacted with the polyol may be from about 1 to about 30 moles of epoxide per mole of polyol.
[0067] Examples of suitable polyols which may be partially or fully (meth)acrylated include organic compounds containing two, three, four, five, six, or more hydroxyl groups per mole, such as ethylene glycol, 1,2- or 1,3-propylene glycol, 1,2-, 1,3-, or 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, neopentyl glycol, cyclohexane-1,4-dimethanol, norbornene dimethanol, norcyclopentane-1,10-dimethanol, norbornene ... Camphanedimethanol, tricyclodecanediol, tricyclodecane dimethanol, bisphenol A, B, F, or S, hydrogenated bisphenol A, B, F, or S, trimethylolpropane, di(trimethylolpropane), triethylolpropane, pentaerythritol, di(pentaerythritol), glycerol, di-, tri-, or tetraethylene glycol, di-, tri-, or tetrapropylene glycol, di-, tri-, or tetrabutylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, poly(ethylene glycol-co-propylene glycol), polycaprolactone polyols, sugar alcohols, and alkoxylated (e.g., ethoxylated and / or propoxylated) derivatives thereof.
[0068] In particular, the monomer (M1) can be selected from: (meth)acrylates of aliphatic polyols, (meth)acrylates of alkoxylated aliphatic polyols, (meth)acrylates of alcohols containing aromatic rings, and (meth)acrylates of alcohols containing aromatic rings alkoxylated. Particularly preferred are methacrylates of aliphatic polyols, methacrylates of alkoxylated aliphatic polyols, methacrylates of alcohols containing aromatic rings, and methacrylates of alcohols containing aromatic rings alkoxylated.
[0069] Monomer (M1) may be a monomer comprising: a (meth)acrylate group and a silane group, in particular a dialkoxysilane (—O—SiR(OR)2, wherein R is an alkyl group) group, or a trialkoxysilane (—O—Si(OR)3, wherein R is an alkyl group) group. Examples of such compounds include: 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltriisopropoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, (meth)acryloxymethyltrimethoxysilane, (meth)acryloxymethyltriethoxysilane, (meth)acryloxymethylmethyldimethoxysilane, (meth)acryloxymethylmethyldiethoxysilane, and 3-(meth)acryloxypropyltri(2-methoxyethoxy)silane.
[0070] Monomer (M1) may be a monomer comprising a (meth)acrylate group and a ketone group. Examples of such compounds include: 2-(acetoacetoxy)ethyl(meth)acrylate, 2-(acetoacetoxy)propyl(meth)acrylate, 3-(acetoacetoxy)propyl(meth)acrylate, 4-(acetoacetoxy)butyl(meth)acrylate, 2,3-di(acetoacetoxy)propyl(meth)acrylate, diacetone(meth)acrylate, and acetonyl(meth)acrylate.
[0071] The monomer (M1) may be a monomer comprising a (meth)acrylate group and an epoxy group. Examples of such compounds are glycidyl (meth)acrylate and epoxidized dicyclopentadienyl (meth)acrylate.
[0072] The monomer (M1) can be represented by the following formula (I):
[0073]
[0074] in
[0075] R1 is H or methyl, preferably R1 is methyl;
[0076] L is a (m+n)-valent linker; it is preferably selected from alkylene, alkoxylated alkylene, polyoxyalkylene, or polyester;
[0077] M is a functional group selected from hydroxyl, silane, ketone, and epoxy;
[0078] x is 0, 1, 2, or 3;
[0079] y is 1, 2, 3, 4, 5, or 6;
[0080] The condition is that x+y≥2.
[0081] In particular, the monomer (M1) may be represented by the following formula (II):
[0082]
[0083] in
[0084] Each R1 is independently H or methyl, preferably R1 is methyl;
[0085] L is a divalent linker selected from the group consisting of an alkylene group, an alkoxylated alkylene group, a polyoxyalkylene group, or a polyester;
[0086] x is 0 or 1;
[0087] y is 1 or 2;
[0088] The condition is, x+y=2.
[0089] In formula (II), L may be a divalent linker selected from one of the following formulae:
[0090] -(CR3R'3) a -,-[(CR4R'4) b -O] c -(CR4R'4) b -,
[0091] -[(CR5R'5) d -O] e -(CR6R'6) f -[O-(CR5R'5) d’ ] e’
[0092] -[(CR7R'7) g -C(=O)O] h -[(CR8R'8) i -O] j -(CR8R'8) i -[OC(=O)-(CR7R'7) g’ ] h’ -;
[0093] in
[0094] R3, R'3, R4, R'4, R5, R'5, R6, R'6, R7, R'7, R8, and R'8 are independently H or alkyl, in particular H or methyl;
[0095] a and f are independently 2 to 20, especially 2 to 10;
[0096] b, d, d', and i are independently 2 to 6, especially 2 to 4;
[0097] c is 1 to 20, especially 1 to 10;
[0098] e and e' are independently 0 to 20, especially 0 to 10, provided that at least one of e and e' is not 0;
[0099] g and g' are independently 3 to 12, especially 5;
[0100] h and h' are independently 0 to 20, especially 0 to 10, provided that at least one of h and h' is not 0
[0101] j is 0-20, specifically 0-10.
[0102] In formula (II), L may be a divalent linker selected from the following: alkylene, such as ethylene, 1,3-propanediyl, 1,3-butanediyl, 1,4-butanediyl, 1,5-pentanediyl, 1,6-hexanediyl, 1,10-decanediyl, 3-methyl-1,5-pentanediyl, 2,2-dimethyl-1,3-propanediyl; alkoxylated (especially ethoxylated and / or propoxylated) derivatives of the aforementioned alkylene; residues of di-, tri-, tetra- or poly(poly)oxyalkylene without OH groups, such as: di-, tri- or tetraethylene glycol, di-, tri- or tetrapropylene glycol, di-, tri- or tetrabutylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, poly(ethylene glycol-co-propylene glycol); and esterified (especially by ring-opening polymerization of lactones) derivatives of the aforementioned oxyalkylene.
[0103] Alternatively, monomer (M1) may be represented by the following formula (III):
[0104]
[0105] in
[0106] Each R1 is independently H or methyl, preferably R1 is methyl;
[0107] L is a trivalent or tetravalent linker selected from the group consisting of an alkylene group, an alkoxylated alkylene group, a polyoxyalkylene group, or a polyester;
[0108] x is 0, 1, 2, or 3;
[0109] y is 1, 2, 3, or 4;
[0110] The condition is that x+y=3 or 4.
[0111] In formula (III), L may be a trivalent linker corresponding to formula (IV) or a tetravalent linker corresponding to formula (V) or (VI):
[0112]
[0113] in
[0114] R p and R' p are independently H or methyl;
[0115] R 10 is selected from H, alkyl, and alkoxy, especially R 10 is an alkyl group;
[0116] n, n', and n" are independently 0 to 2, provided that at least 2 of n, n', and n" are not 0, in particular n, n', and n" are all 1, or n is 0 and n' and n" are 1;
[0117] o, o', and o" are independently 2 to 4, especially 2;
[0118] p, p', and p" are independently 0 to 10, especially 0 to 6;
[0119]
[0120] in
[0121] R q and R' q are independently H or methyl;
[0122] q, q', q", and q'" are independently 0 to 2, provided that at least 3 of q, q', q", and q'" are not 0, and in particular, fq, q', q", and q'" are all 1,
[0123] r, r', r", and r'" are independently 2 to 4, especially 2;
[0124] s, s', s", and s'" are independently 0 to 10, especially 1 to 6;
[0125]
[0126] in
[0127] R r and R' r are independently H or methyl;
[0128] t, t', t", and t'" are independently 2 to 4, especially 2;
[0129] u, u', u", and u'" are independently 0 to 10, specifically 1 to 6.
[0130] In one embodiment, the monomer (M1) can be represented by the following formula:
[0131]
[0132] in
[0133] R1 and R2 are independently H or methyl, preferably R1 and R2 are methyl;
[0134] L is a divalent group selected from an alkylene group or a polyoxyalkylene group;
[0135] In particular, L is a divalent group selected from:
[0136] -(CR3R'3) a -,-[(CR4R'4) b -O] c-(CR4R'4) b -,
[0137] -[(CR5R'5) d -O] e -(CR6R'6) f -[O-(CR5R'5) d’ ] e’
[0138] in
[0139] R3, R'3, R4, R'4, R5, R'5, R6 and R'6 are independently H or alkyl, in particular H or methyl;
[0140] a is 2 to 20, especially 2 to 10;
[0141] f is 2 to 20, especially 2 to 6;
[0142] b, d, d' are independently 2 to 6, especially 2 to 4;
[0143] c is 1 to 20, especially 1 to 10;
[0144] e and e' are independently 0 to 20, provided that at least one of e and e' is not 0, in particular e and e' are independently 1 to 10;
[0145] More particularly L is a divalent radical chosen from ethylene, 1,3-propylene, 1,4-butylene, 1,3-butylene, 1,5-pentamethylene, 1,6-hexamethylene, the residue of di-, tri- or tetraethylene glycol, the residue of di-, tri- or tetrapropylene glycol, the residue of di-, tri- or tetrabutylene glycol, and mixtures thereof.
[0146] In another embodiment, the monomer (M1) can be represented by the following formula:
[0147]
[0148] in
[0149] R 13 , R 14 , and R 15 are independently H or methyl, preferably R 13 , R 14 , and R 15 is methyl;
[0150] L is a trivalent group selected from an alkylene group or a polyoxyalkylene group.
[0151] In particular, L may be a trivalent group represented by the formula:
[0152]
[0153] in
[0154] R p and R' p are independently H or methyl;
[0155] R 10 is selected from H, alkyl, and alkoxy, especially R 10 is an alkyl group;
[0156] n, n', and n" are independently 0 to 2, provided that at least 2 of n, n', and n" are not 0, in particular n, n', and n" are all 1, or n is 0 and n' and n" are 1;
[0157] o, o', and o" are independently 2 to 6, especially 2 to 4;
[0158] p, p′, and p″ are independently 0 to 10, specifically 0 to 4.
[0159] Representative (but non-limiting) examples of suitable monomers (M1) include: ethylene glycol di(meth)acrylate, 1,2 or 1,3-propylene glycol di(meth)acrylate, 1,2-, 1,3-, or 1,4-butanediol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, di-, tri-, or tetraethylene glycol di(meth)acrylate, di-, tri-, or tetrapropylene glycol di(meth)acrylate, di-, tri-, or tetrabutanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, di-, tri-, or tetra- Acrylates, cyclohexanedimethanol di(meth)acrylates, bisphenol A, B, F, or S di(meth)acrylates, hydrogenated bisphenol A, B, F, or S di(meth)acrylates, tricyclodecane dimethanol di(meth)acrylates, trimethylolpropane tri(meth)acrylates, di(trimethylolpropane) tetra(meth)acrylates, triethylolpropane tri(meth)acrylates, glycerol tri(meth)acrylates, pentaerythritol tetra(meth)acrylates, polyethylene glycol di(meth)acrylates, polypropylene glycol di(meth)acrylates, polytetramethylene glycol di(meth)acrylates, poly(ethylene glycol-co-propylene glycol) di(meth)acrylates, polycaprolactone di(meth)acrylates, isosorbide di(meth)acrylates, and alkoxylated (e.g., ethoxylated, propoxylated) derivatives thereof. Particularly preferred are methacrylated derivatives of the above compounds.
[0160] Examples of suitable monomers (M1) having hydroxyl groups as functional groups include: polycaprolactone (meth) acrylate, 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, di-, tri- or tetraethylene glycol mono(meth) acrylate, di-, tri- or tetrapropylene glycol mono(meth) acrylate, polyethylene glycol mono(meth) acrylate, polypropylene glycol mono(meth) acrylate, pentaerythritol tri(meth) acrylate, glycerol di(meth) acrylate, and alkoxylated (e.g. ethoxylated, propoxylated) derivatives thereof. Particularly preferred are methacrylated derivatives of the above compounds.
[0161] In one embodiment, monomer (M1) is selected from: ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, and 1,6-hexanediol dimethacrylate; even more preferably, monomer (M1) is tetraethylene glycol dimethacrylate. In another embodiment, monomer (M1) is selected from: polycaprolactone methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, di-, tri-, or tetraethylene glycol monomethacrylate, even more preferably, monomer (M1) is 2-hydroxypropyl methacrylate.
[0162] The composition (P1) may comprise 15 to 80%, specifically 20 to 75%, more specifically 25 to 70% by weight of monomer (M1), based on the weight of the composition (P1).
[0163] Oligomer (O1)
[0164] The composition (P1) comprises an oligomer (O1). The composition (P1) comprises a mixture of a plurality of oligomers (O1).
[0165] The oligomer (O1) carries at least 2 ethylenic unsaturations, preferably 2 to 10 ethylenic unsaturations. As used herein, the term "ethylenic unsaturation" means a polymerizable carbon-carbon double bond. In particular, the oligomer (O1) carries up to 2 ethylenic unsaturations selected from acrylate, methacrylate, vinyl, and allyl, and mixtures thereof.
[0166] In a preferred embodiment, the oligomer (O1) carries at least 2, preferably 2 to 10 (meth)acrylate groups. In one embodiment, the oligomer (O1) carries at least 2, preferably 2 to 10 methacrylate groups. In another embodiment, the oligomer (O1) carries at least 2, preferably 2 to 10 acrylate groups.
[0167] The oligomer (O1) has a weight average molecular weight (Mw) of 421 to 10000 g / mol, specifically 450 to 3000 g / mol.
[0168] The oligomer (O1) may exhibit a Tg of 10 to 200° C., specifically 15 to 150° C., more specifically 20 to 130° C. In one embodiment, the oligomer (O1) exhibits a Tg of 50 to 200° C., specifically 80 to 150° C., more specifically 90 to 130° C. In another embodiment, the oligomer (O1) exhibits a Tg of 10 to 100° C., specifically 15 to 80° C., more specifically 20 to 60° C.
[0169] Preferably, the oligomer (O1) is selected so as to have a sufficient concentration of ethylenic unsaturation. For example, the oligomer (O1) may have a polymerizable carbon-carbon double bond content (%C=C 低聚物 ), based on the weight of the oligomer (O1).
[0170] %C=C 低聚物 It can be determined according to the following formula:
[0171]
[0172] in
[0173] f 低聚物 is the number of polymerizable carbon-carbon double bonds of the oligomer (O1); and
[0174] M 低聚物 is the weight average molecular weight of the oligomer (O1), in g / mol. In one embodiment, the oligomer (O1) may be selected from epoxy (meth)acrylates, urethane (meth)acrylates, polyester (meth)acrylates, polyether (meth)acrylates, (meth)acrylated poly (meth)acrylates, unsaturated polyesters, polybutadiene, vinyl ethers, amine-modified and sulfide-modified derivatives of the aforementioned oligomers, and mixtures thereof.
[0175] In a preferred embodiment, the oligomer (O1) is selected from the group consisting of epoxy (meth) acrylates, urethane (meth) acrylates, polyester (meth) acrylates, polyether (meth) acrylates, and mixtures thereof. Advantageously, the oligomer (O1) is selected from the group consisting of epoxy methacrylates, urethane methacrylates, polyester methacrylates, polyether methacrylates, and mixtures thereof.
[0176] Examples of suitable epoxy (meth)acrylates include reaction products of acrylic acid or methacrylic acid or mixtures thereof with epoxy resins (polyglycidyl ethers or esters). The epoxy resins may be selected in particular from bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, bisphenol S diglycidyl ether, brominated bisphenol A diglycidyl ether, brominated bisphenol F diglycidyl ether, brominated bisphenol S diglycidyl ether, epoxy novolac resins, hydrogenated bisphenol A diglycidyl ether, hydrogenated bisphenol F diglycidyl ether, hydrogenated bisphenol S diglycidyl ether, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexyl Alkanecarboxylates, 2-(3,4-epoxycyclohexyl-5,5-spiro-3,4-epoxy)cyclohexane-1,4-dioxane, bis(3,4-epoxycyclohexylmethyl)adipate, vinylcyclohexene oxide, 4-vinylepoxycyclohexane, bis(3,4-epoxy-6-methylcyclohexylmethyl)adipate, 3,4-epoxy-6-methylcyclohexyl-3',4'-epoxy-6'-methylcyclohexanecarboxylate, methylenebis(3,4-epoxycyclohexane), dicyclopentadiene diepoxide, ethylene glycol di(3,4-epoxycyclohexylmethyl) ether, ethylene bis(3,4-epoxycyclohexanecarboxylate), 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, aliphatic polyhydric alcohols (such as ethylene glycol, propylene glycol, and glycerol) are prepared by adding one or more Polyglycidyl ethers of polyether polyols obtained by oxidizing alkylene groups, diglycidyl esters of aliphatic long-chain dibasic acids, monoglycidyl ethers of aliphatic higher alcohols, phenol, cresol, butylphenol, or monoglycidyl ethers of polyether alcohols (the polyether alcohols are obtained by adding oxidized alkylene groups to these compounds), glycidyl esters of higher fatty acids, epoxidized soybean oil, epoxybutyl stearic acid, epoxyoctyl stearic acid, epoxidized linseed oil, epoxidized polybutadiene, and the like.
[0177] Exemplary urethane (meth)acrylates (sometimes also referred to as "polyurethane (meth)acrylates") include urethanes based on aliphatic, cycloaliphatic and / or aromatic polyester polyols, polyether polyols and polycarbonate polyols, and aliphatic, cycloaliphatic and / or aromatic polyester diisocyanates and polyether diisocyanates terminated with (meth)acrylate end groups. In various embodiments, the urethane (meth) acrylate can be obtained by reacting an aliphatic, alicyclic and / or aromatic polyisocyanate (e.g., diisocyanate, triisocyanate) with a polyester polyol, polyether polyol, polycarbonate polyol, polycaprolactone polyol, polydimethylsiloxane polyol, or polybutadiene polyol, or a combination thereof, which is terminated with an OH group, to form an isocyanate functionalized oligomer, which is then reacted with a hydroxyl functionalized (meth) acrylate (such as hydroxyethyl (meth) acrylate or hydroxypropyl (meth) acrylate) to provide a terminal (meth) acrylate group. For example, the urethane (meth) acrylate can contain two, three, four, or more (meth) acrylate functional groups per molecule. Other addition orders can also be practiced to prepare polyurethane (meth) acrylates, which are known in the art. For example, the hydroxyl-functional (meth) acrylate may first react with polyisocyanates to obtain isocyanate-functional (meth) acrylates, which may then react with polyester polyols, polyether polyols, polycarbonate polyols, polycaprolactone polyols, polydimethylsiloxane polyols, polybutadiene polyols, or combinations thereof, which are OH-terminated. In yet another embodiment, polyisocyanates may first react with polyols (including any of the aforementioned types of polyols) to obtain isocyanate-functional polyols, which may then react with hydroxyl-functional (meth) acrylates to produce polyurethane (meth) acrylates. Alternatively, all compounds may be combined and reacted simultaneously.
[0178] Exemplary polyester (meth) acrylates include the reaction products of acrylic acid or methacrylic acid or mixtures thereof with polyester polyols terminated with hydroxyl groups. The reaction process (process) can be carried out so that a significant concentration of residual hydroxyl groups remain in the polyester (meth) acrylate, or the reaction process can be carried out so that all or substantially all hydroxyl groups of the polyester polyol have been (meth) acrylated. The polyester polyol can be prepared by the polycondensation reaction of a polyhydroxyl functional component (especially a diol) and a polycarboxylic acid functional compound (especially a dicarboxylic acid or anhydride). To prepare the polyester (meth) acrylate, the hydroxyl groups of the polyester polyol are then partially or completely esterified by reaction with (meth) acrylic acid, (meth) acryloyl chloride, (meth) acrylic anhydride, etc. Polyester (meth) acrylates can also be synthesized by reacting a hydroxyl-containing (meth) acrylate such as a hydroxyalkyl (meth) acrylate (e.g., hydroxyethyl acrylate) with a polycarboxylic acid. The polyhydroxyl functional and polycarboxylic acid functional components can each have a linear, branched, alicyclic or aromatic structure, and can be used alone or as a mixture.
[0179] Exemplary polyether (meth) acrylates include, but are not limited to, condensation products of acrylic acid or methacrylic acid or mixtures thereof with polyether alcohols as polyether polyols. Suitable polyether alcohols may be linear or branched species containing ether-bonded terminal hydroxyl groups. Polyether alcohols may be prepared by ring-opening polymerization of epoxides and other heterocyclic compounds containing oxygen (e.g., ethylene oxide, 1,2-propylene oxide, butylene oxide, tetrahydrofuran, and combinations thereof) with starter molecules. Suitable starter molecules include water, hydroxyl functional materials, polyester polyols, and amines. Polyether alcohols may also be obtained by condensation of glycols such as ethylene glycol.
[0180] Any of the above-mentioned types of oligomers may be modified by amines or sulfides (e.g., thiols) following procedures known in the art. Such amine- and sulfide-modified oligomers may be prepared, for example, by reacting a relatively small portion (e.g., 2-15%) of the (meth)acrylate functional groups present in the base oligomer with an amine (e.g., a secondary amine) or a sulfide (e.g., a thiol), wherein the modifying compound is added to the carbon-carbon double bond of the (meth)acrylate in a Michael addition reaction.
[0181] The composition (P1) may comprise 15 to 80%, specifically 20 to 75%, more specifically 25 to 70% by weight of oligomer (O1), based on the weight of the composition (P1).
[0182] Additives (AD)
[0183] The composition (P1) comprises an additive (AD).
[0184] Additives (AD) include:
[0185] a) a multistage polymer (MP1), said multistage polymer (MP1) comprising:
[0186] a1) one grade (SA1) comprising a polymer (A1) having a glass transition temperature of less than 10°C; and
[0187] a2) one stage (SA2) comprising a polymer (A2) having a glass transition temperature of at least 60°C; and
[0188] b) A thermoplastic polymer (B1 ) having a glass transition temperature of at least 30°C.
[0189] The composition (P1) may comprise from 1 to 13%, specifically from 1.5 to 10%, more specifically from 2.5 to 8%, even more specifically from 3.5 to 6% by weight of additive (AD), based on the weight of the composition (P1).
[0190] The additive (AD) may comprise at least 4%, at least 5%, at least 6%, at least 7%, at least 8%, at least 9%, or at least 10% by weight of the thermoplastic polymer (B1), based on the total weight of the multistage polymer (MP1) and the thermoplastic polymer (B1).
[0191] The additive (AD) may comprise up to 40%, up to 35%, up to 30%, up to 28%, up to 25%, up to 22%, or up to 20% by weight of the thermoplastic polymer (B1), based on the total weight of the multistage polymer (MP1) and the thermoplastic polymer (B1).
[0192] The additive (AD) may comprise 4 to 40%, 5 to 35%, 6 to 30%, 7 to 28%, 8 to 25%, 9 to 22%, or 10 to 20% by weight of the thermoplastic polymer (B1), based on the total weight of the multistage polymer (MP1) and the thermoplastic polymer (B1).
[0193] The multistage polymer (MP1) may be in the form of polymeric particles, in particular in the form of spherical particles.The multistage polymer (MP1) may be referred to as particles, in particular core / shell particles or multistage particles.
[0194] The particles may have a weight average particle size (diameter) between 15 nm and 900 nm. In particular, the particles may have a weight average particle size between 20 nm and 800 nm, more particularly between 25 nm and 600 nm, even more particularly between 30 nm and 550 nm, still more particularly between 35 nm and 500 nm, or between 40 nm and 400 nm, or between 75 nm and 350 nm, or between 80 nm and 300 nm.
[0195] In one embodiment, the core / shell particles may be agglomerated in the form of a polymer powder comprising a plurality of core / shell particles.
[0196] The multi-stage polymer (MP1) of the additive (AD) has at least two stages (SA1) and (SA2). The stages (SA1) and (SA2) have different polymer compositions.
[0197] Level (SA1) may be referred to as a first level and level (SA2) may be referred to as a second level. The terms "first level" and "second level" refer to the order in which the levels are formed. Accordingly, the first level is formed before the second level. The use of the term "first level" does not exclude the existence of additional levels formed before the first level. The use of the term "second level" does not exclude the existence of intermediate levels formed between the first level and the second level.
[0198] The multistage polymer (MP1) may be obtained by a multistage process, such as a process comprising two, three or more stages.
[0199] Stage (SA1) may form the core of the particle. Stage (SA2) may form a shell around stage (SA1) of the particle. Optionally, the particle may comprise additional stages, which may form an intermediate layer between stage (SA1) and stage (SA2). Optionally, the particle may comprise additional stages that may form a shell around stage (SA2) of the particle. Optionally, the particle may comprise additional stages before stage (SA1) so that stage (SA1) will also be a kind of shell, for example on a seed.
[0200] Preferably, the stage (SA1) comprising polymer (A1) is the first of the at least two stages and the stage (SA2) comprising polymer (A2) is grafted onto the stage (SA1) comprising polymer (A1) or onto a further optional intermediate layer.
[0201] In particular, the polymer (A1) having a glass transition temperature below 10°C in stage (SA1) is not in an outer layer of the multistage polymer. Accordingly, polymer (A1) is not produced in the last stage of the multistage process. The polymer (A1) having a glass transition temperature below 10°C in stage (A1) is either in the core of the multistage particle or in one of the inner layers. Preferably, stage (SA1) is the innermost layer of the multistage polymer (MP1). In other words, the stage (SA1) comprising polymer (A1) may be the core of the multistage polymer (MP1).
[0202] In a first preferred embodiment, the stage (SA2) comprising polymer (A2) is an outer layer of the multistage polymer. In this embodiment, the thermoplastic polymer (B1 ) is not part of the multistage polymer.
[0203] In a second preferred embodiment, the stage (SA2) comprising polymer (A2) is the middle layer of the multistage polymer and the outer layers of the multistage polymer are further stages (SB1) comprising a thermoplastic polymer (B1) having a glass transition temperature above 30°C.
[0204] According to this embodiment, the multistage polymer (MP1) has a multilayer structure comprising a first stage (SA1) comprising a polymer (A1) having a glass transition temperature below 10°C, a second stage (SA2) comprising a polymer (A2) having a glass transition temperature above 60°C, and a third stage (SB1) comprising a thermoplastic polymer (B1) having a glass transition temperature above 30°C. In this embodiment, at least a portion of component b) of the additive (AD) is combined with component a) of the additive (AD). Accordingly, at least a portion of component b) may be a further stage of the multistage polymer comprising stage (SA1) and stage (SA2). This embodiment is further explained in the following section on a multistage process for preparing a multistage polymer (MP1) and an additive (AD).
[0205] In a preferred embodiment, the multistage polymer (MP1) comprises a plurality of core / shell particles as defined above.
[0206] Polymer (A1)
[0207] The polymer (A1) has a glass transition temperature of less than 10°C.
[0208] In a first embodiment, polymer (A1) may be a (meth)acrylic polymer comprising at least 50 wt. %, preferably at least 60 wt. %, more preferably at least 70 wt. %, even more preferably at least 80 wt. %, of polymerizable units derived from acrylic monomers, based on the weight of polymer (A1).
[0209] The acrylic polymerizable units in the polymer (A1) of the first embodiment may be derived from acrylic monomers selected from C1 to C18 alkyl acrylates or mixtures thereof. In particular, the acrylic polymerizable units in the polymer (A1) may be derived from acrylic monomers selected from C2 to C12 alkyl acrylates or mixtures thereof. More particularly, the acrylic polymerizable units in the polymer (A1) may be derived from acrylic monomers selected from C2 to C8 alkyl acrylates or mixtures thereof. Even more particularly, the acrylic polymerizable units in the polymer (A1) may be derived from acrylic monomers selected from propyl acrylate, isopropyl acrylate, butyl acrylate, tert-butyl acrylate, and mixtures thereof. Still more particularly, the acrylic polymerizable units in the polymer (A1) may be derived from butyl acrylate.
[0210] The polymer (A1 ) of the first embodiment may advantageously comprise at least 70 wt.-%, based on the weight of polymer (A1 ), of polymerizable units derived from C2 to C8 alkyl acrylate.
[0211] The polymer (A1) of the first embodiment may further comprise a polymerizable unit derived from a comonomer (one or more comonomers) copolymerizable with the aforementioned acrylic monomer, as long as the polymer (A1) has a glass transition temperature of less than 10° C. In particular, the polymer (A1) may further comprise a polymerizable unit derived from a comonomer (one or more comonomers) selected from a (meth)acrylic monomer and / or a vinyl monomer. More particularly, the polymer (A1) may further comprise a polymerizable unit derived from a comonomer (one or more comonomers) selected from methyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, and a mixture thereof, as long as the polymer (A1) has a glass transition temperature of less than 10° C.
[0212] The polymer (A1) of the first embodiment may advantageously be a homopolymer of butyl acrylate.
[0213] The glass transition temperature Tg of the polymer (A1) of the first embodiment may be between -100°C and less than 10°C, specifically between -80°C and 0°C, more specifically between -80°C and -20°C, even more specifically between -70°C and -20°C.
[0214] In a second embodiment, polymer (A1) may comprise at least 50 wt. %, based on the weight of polymer (A1), of polymerizable units derived from isoprene, butadiene, and mixtures thereof.
[0215] The polymer (A1) of the second embodiment can advantageously be selected from: isoprene homopolymers, butadiene homopolymers, isoprene-butadiene copolymers, copolymers of isoprene with up to 98% by weight of vinyl monomers, and copolymers of butadiene with up to 98% by weight of vinyl monomers. The vinyl monomers can be selected from: styrene, alkylstyrenes, acrylonitrile, alkyl (meth)acrylates, and mixtures thereof.
[0216] The polymer (A1) of the second embodiment may advantageously be a butadiene homopolymer.
[0217] The glass transition temperature Tg of the polymer (A1) of the second embodiment may be between -100°C and less than 10°C, specifically between -90°C and 0°C, more specifically between -85°C and 0°C, even more specifically between -80°C and -20°C.
[0218] In the third embodiment, the polymer (A1) may be a silicone rubber-based polymer. The silicone rubber-based polymer may be, for example, polydimethylsiloxane.
[0219] The glass transition temperature Tg of the polymer (A1) of the third embodiment may be between -150°C and 0°C, specifically between -145°C and -5°C, more specifically between -140°C and -15°C, even more specifically between -135°C and -25°C.
[0220] Polymer (A2)
[0221] The polymer (A2) has a glass transition temperature of at least 60°C.
[0222] Polymer (A2) may be a (meth)acrylic polymer comprising at least 50 wt. %, preferably at least 60 wt. %, more preferably at least 70 wt. %, even more preferably at least 80 wt. %, based on the weight of polymer (A2), of polymerizable units derived from ethylenically unsaturated monomers such as (meth)acrylates and / or vinyl monomers, preferably derived from (meth)acrylates.
[0223] The (meth)acrylic polymeric units in polymer (A2) may be derived from (meth)acrylic monomers selected from C1 to C12 alkyl (meth)acrylates and mixtures thereof. In particular, the (meth)acrylic polymeric units in polymer (A2) may be derived from (meth)acrylic monomers selected from C1 to C4 alkyl methacrylates, C1 to C8 alkyl acrylates, and mixtures thereof. More particularly, the (meth)acrylic polymeric units in polymer (A2) may be derived from (meth)acrylic monomers selected from methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, and mixtures thereof. Even more particularly, the (meth)acrylic polymeric units in polymer (A2) may be derived from methyl methacrylate.
[0224] Polymer (A2) may comprise at least 70% by weight of monomeric units derived from C1 to C12 alkyl (meth)acrylate, based on the weight of polymer (A2). More particularly, polymer (A2) may comprise at least 70% by weight of monomeric units derived from C1 to C4 alkyl methacrylate and / or C1 to C8 alkyl acrylate monomers, based on the weight of polymer (A2). Even more particularly, polymer (A2) may comprise at least 70% by weight of monomeric units derived from methyl methacrylate, based on the weight of polymer (A2).
[0225] The polymer (A2) may further comprise polymerizable units derived from a comonomer (one or more comonomers) copolymerizable with the aforementioned (meth)acrylic monomer, as long as the polymer (A2) has a glass transition temperature of at least 60° C. In particular, the polymer (A2) may further comprise polymerizable units derived from a comonomer (one or more comonomers) selected from vinyl monomers (e.g., styrene).
[0226] The glass transition temperature Tg of polymer (A2) may be between 60 and 150°C, specifically between 80 and 150°C, more specifically between 90 and 150°C, even more specifically between 100 and 150°C.
[0227] In certain embodiments, polymer (A2) is cross-linked. This means that a cross-linking agent is present together with the other monomers (one or more monomers). In one embodiment, the cross-linking agent is divinylbenzene.
[0228] In one embodiment, polymer (A2) comprises a functional comonomer. The functional comonomer may be represented by one of the following formulas (1) and (2):
[0229]
[0230] in
[0231] R 23 Selected from H or CH3;
[0232] R 24 is H or an aliphatic or aromatic group having at least one atom other than C or H;
[0233] R 25 and R 26 is independently H or an aliphatic or aromatic group.
[0234] Preferably, the functional monomer of formula (1) or (2) is selected from glycidyl (meth) acrylate; (meth) acrylic acid; amides derived from (meth) acrylic acid, such as dimethyl acrylamide; 2-methoxyethyl (meth) acrylate; 2-aminoethyl (meth) acrylate which may be optionally quaternized; (meth) acrylate monomers containing phosphonate (root) or phosphate (root) groups; alkyl imidazolidinone (meth) acrylates; polyethylene glycol (meth) acrylates; and mixtures thereof. More particularly, the polyethylene glycol group of the polyethylene glycol (meth) acrylate has a weight average molecular weight ranging from 400 g / mol to 10000 g / mol.
[0235] Thermoplastic polymer (B1)
[0236] The thermoplastic polymer (B1) may be a (meth)acrylic polymer.
[0237] As used herein, the term "thermoplastic polymer" means a polymer that becomes liquid, or more liquid or less viscous, when heated and that can adopt new shapes by the application of heat and pressure.
[0238] As used herein, the term "(meth)acrylic polymer" means a polymer comprising polymerized units derived from one or more (meth)acrylic monomers, wherein the (meth)acrylic monomers constitute 50% by weight or more of the (meth)acrylic polymer. As used herein, the term "(meth)acrylic monomer" means any type of polymerizable monomer containing one or more acrylic and / or methacrylic functional groups.
[0239] Thermoplastic polymer (B1) may be a homopolymer or a copolymer. Wherein "copolymer" refers to a polymer containing polymerized units derived from two or more different monomers. Preferably, the thermoplastic polymer (B1) is not grafted onto any other polymer (one or more polymers), or at least a portion of the thermoplastic polymer is not grafted onto any other polymer (one or more polymers).
[0240] In particular, at least a portion of the thermoplastic polymer (B1) is not grafted onto the multistage polymer (MP1). More particularly, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, at least 98%, at least 99%, or 100% by weight of the polymer (B1) is not grafted onto any other polymer (polymers), in particular onto the multistage polymer (MP1), more particularly onto the polymer (A2). The grafting rate can be determined by using a solvent extraction of the polymer (B1) and determining the ungrafted amount by gravimetric measurement before and after the extraction. The ungrafted amount corresponds to the amount (weight) of the polymer (B1) dissolved by the solvent, and the grafted amount corresponds to the amount (weight) of the polymer (B1) that is not dissolved by the solvent and remains on the multistage polymer (MP1).
[0241] Without wishing to be bound by any particular theory, it is believed that when at least a portion of the thermoplastic polymer (B1) is not grafted onto the multistage polymer (MP1), it can at least partially dissociate from the outer surface of the multistage polymer (MP1) and at least partially dissolve in other polymerizable components of the curable composition (particularly the monomers (M1) and oligomers (O1)). This advantageously improves the dispersion of the multistage polymer in the curable composition and reduces agglomeration and / or precipitation of the multistage polymer.
[0242] The thermoplastic polymer (B1) of component (b) of additive (AD) may be of the same or different composition than any polymer present as part of the multistage polymer (MP1) of component (a) of additive (AD). The thermoplastic polymer (B1) of component (b) may be of a different composition than any polymer present as part of the multistage polymer (MP1) of component (a).
[0243] The presence of a thermoplastic polymer (B1) in a curable composition helps to promote the dispersion and stabilization of the multistage polymer (MP1) in both the curable composition and the cured article prepared by the curable composition. In the absence of a thermoplastic polymer (B1), the multistage polymer (MP1) (which is typically in the form of particles) may tend to agglomerate and precipitate from the curable composition (making the curable composition uneven). Thus, it has been found that including a thermoplastic polymer (B1) causes the multistage polymer (MP1) to be uniformly dispersed in the curable composition, which promotes the formation of a uniform cured article prepared by curing the curable composition. After combining the multistage polymer (MP1) with the monomer (M1) and the oligomer (O1), the ideal uniform dispersion of the multistage polymer (MP1) in the matrix is free of agglomerates. Thus, compared to similar compositions not comprising a thermoplastic polymer (B1), a liquid curable composition comprising a thermoplastic polymer (B1), a multistage polymer (MP1), a monomer (M1), and an oligomer (O1) can exhibit better dispersion of the multistage polymer (MP1). Further, compared to similar compositions not comprising a thermoplastic polymer (B1), a liquid curable composition comprising a thermoplastic polymer (B1), a multistage polymer (MP1), a monomer (M1), and an oligomer (O1) can have a lower viscosity.
[0244] The thermoplastic polymer (B1) has a weight average molecular weight Mw of between 10 000 g / mol and 500 000 g / mol.
[0245] The thermoplastic polymer (B1) may have a weight average molecular weight Mw of greater than 10,000 g / mol, preferably greater than 10,500 g / mol, more preferably greater than 11,000 g / mol, still more preferably greater than 12,000 g / mol, advantageously greater than 13,000 g / mol, more advantageously greater than 14,000 g / mol, and still more advantageously greater than 15,000 g / mol.
[0246] The thermoplastic polymer (B1) may have a weight average molecular weight Mw of less than 500000 g / mol, preferably less than 450000 g / mol, more preferably less than 400000 g / mol, still more preferably less than 400000 g / mol, advantageously less than 350000 g / mol, more advantageously less than 300000 g / mol, still more advantageously less than 250000 g / mol, and most advantageously less than 200000 g / mol.
[0247] The thermoplastic polymer (B1) may have a weight average molecular weight Mw of between 10500 g / mol and 450000 g / mol, more preferably between 11000 g / mol and 400000 g / mol, even more preferably between 12000 g / mol and 350000 g / mol, advantageously between 13000 g / mol and 300000 g / mol, more advantageously between 14000 g / mol and 250000 g / mol, and most advantageously between 15000 g / mol and 200000 g / mol.
[0248] In a first embodiment, the weight average molecular weight Mw of the thermoplastic polymer (B1) may be between 15000 g / mol and 300000 g / mol, more preferably between 15000 g / mol and 200000 g / mol, even more preferably between 15000 g / mol and 190000 g / mol, advantageously between 15000 g / mol and 180000 g / mol, more advantageously between 15000 g / mol and 160000 g / mol, and most advantageously between 15000 g / mol and 150000 g / mol.
[0249] In a second embodiment, the weight average molecular weight Mw of the thermoplastic polymer (B1) may be between 15000 g / mol and 450000 g / mol, more preferably between 18000 g / mol and 400000 g / mol, even more preferably between 20000 g / mol and 350000 g / mol, advantageously between 22000 g / mol and 300000 g / mol, more advantageously between 25000 g / mol and 250000 g / mol, and most advantageously between 30000 g / mol and 200000 g / mol.
[0250] The weight average molecular weight (Mw) of the thermoplastic polymer (B1) can be selected according to the first or second embodiment depending on the viscosity obtained for the curable composition. If the viscosity should be low, or if an additional rheology modifier is present, the second embodiment is preferred. If the viscosity should be higher or no additional rheology modifier is present, the first embodiment is preferred.
[0251] The glass transition temperature Tg of the thermoplastic polymer (B1 ) may be between 30 and 150°C, specifically between 40 and 150°C, more specifically between 45 and 150°C, even more specifically between 50 and 150°C.
[0252] Preferably, the thermoplastic polymer (B1) comprises polymeric units derived from (meth)acrylic monomers, particularly derived from C1 to C12 alkyl (meth)acrylate monomers, more particularly derived from C1 to C4 alkyl methacrylate and / or C1 to C8 alkyl acrylate monomers, even more particularly derived from methyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, and mixtures thereof.
[0253] Still more preferably, the thermoplastic polymer (B1) comprises at least 70% by weight of polymerizable units derived from C1 to C12 alkyl (meth)acrylate monomers, based on the weight of the thermoplastic polymer (B1). Advantageously, the thermoplastic polymer (B1) comprises at least 80% by weight of polymerizable units derived from C1 to C4 alkyl methacrylate and / or C1 to C8 alkyl acrylate monomers, based on the weight of the thermoplastic polymer (B1).
[0254] In a first preferred embodiment, the thermoplastic polymer (B1) comprises 80 to 100% by weight of polymerizable units derived from methyl methacrylate, preferably the thermoplastic polymer (B1) comprises 80 to 99.9% by weight of polymerizable units derived from methyl methacrylate and 0.1 to 20% by weight of polymerizable units derived from C1 to C8 alkyl acrylate monomers, based on the weight of the thermoplastic polymer (B1). Advantageously, the C1 to C8 alkyl acrylate monomers are selected from methyl acrylate, ethyl acrylate, and butyl acrylate.
[0255] In another embodiment, the thermoplastic polymer (B1) further comprises polymerizable units derived from a functional comonomer. The functional comonomer may be represented by one of the formulas (1) and (2) as defined above for polymer (A2). Preferably, the functional monomer having formula (1) or (2) is selected from: glycidyl (meth)acrylate; (meth)acrylic acid; amides derived from (meth)acrylic acid, such as dimethylacrylamide; 2-methoxyethyl (meth)acrylate; 2-aminoethyl (meth)acrylate, which may be optionally quaternized; (meth)acrylate monomers comprising phosphonate or phosphate groups; alkyl imidazolidinone (meth)acrylate; polyethylene glycol (meth)acrylate; and mixtures thereof. More particularly, the polyethylene glycol group of the polyethylene glycol (meth)acrylate has a weight average molecular weight ranging from 400 g / mol to 10000 g / mol.
[0256] In particular, the thermoplastic polymer (B1) may comprise between 0% and 50% by weight of polymerizable units derived from functional monomers, based on the weight of the thermoplastic polymer (B1). Preferably, the thermoplastic polymer (B1) comprises between 0% and 30% by weight, more preferably between 1% and 30% by weight, still more preferably between 2% and 30% by weight, advantageously between 3% and 30% by weight, more advantageously between 5% and 30% by weight, and most advantageously between 5% and 30% by weight of polymerizable units derived from functional monomers, based on the weight of the thermoplastic polymer (B1).
[0257] Preferably, the thermoplastic polymer (B1) is not crosslinked.
[0258] Multistage process for the preparation of multistage polymers (MP1) and additives (AD)
[0259] The multistage polymer (MP1) is obtainable by a multistage process comprising at least two stages. Components a1) and a2) are part of the multistage polymer (MP1). At least a portion of component b) may also be part of the multistage polymer (MP1), in particular as a further stage of the multistage polymer (MP1). Alternatively, component b) may be agglomerated with the multistage polymer (MP1). Alternatively, at least a portion of component b) is grafted onto the multistage polymer (MP1), and at least a portion of component b) is not grafted onto the multistage polymer (MP1).
[0260] Preferably, the polymer (A1 ) having a glass transition temperature below 10°C produced during stage (SA1 ) is produced before stage (SA2) or is the first stage of said multi-stage process.
[0261] Preferably, the polymer (A2) having a glass transition temperature of at least 60° C. produced during stage (SA2) is produced after stage (SA1) of said multistage process.
[0262] In a first preferred embodiment, a thermoplastic polymer (B1) having a glass transition temperature of at least 30°C is obtained by a process for providing polymeric particles of a thermoplastic polymer (B1). The weight average particle size (diameter) of the thermoplastic polymer (B1) particles may be between 15 nm and 900 nm, preferably between 20 nm and 800 nm, more preferably between 25 nm and 600 nm, even more preferably between 30 nm and 550 nm, still more preferably between 35 nm and 500 nm, advantageously between 40 nm and 400 nm, more advantageously between 75 nm and 350 nm, and even more advantageously between 80 nm and 300 nm. The thermoplastic polymer (B1) particles may be agglomerated with multistage polymer (MP1) particles to provide a polymer powder comprising a plurality of (MP1) particles and a plurality of (B1) particles. In this embodiment, the (MP1) particles and the (B1) particles are different from each other. Accordingly, the thermoplastic polymer (B1) is not grafted onto the multistage polymer (MP1).
[0263] In a second preferred embodiment, the thermoplastic polymer (B1) having a glass transition temperature of at least 30° C. is the outer layer of the polymer particles having a multilayer structure, in other words the multistage polymer (MP1).
[0264] Thermoplastic polymers (B1) having a glass transition temperature of more than 30° C. may be produced after stage (SA2) of the multistage process, during stage (SB1). Additional intermediate stages may be present, either between stage (SA1) and stage (SA2) and / or between stage (SA2) and stage (SB1).
[0265] When the thermoplastic polymer (B1) is part of a multistage polymer (MP1), for example as an outer layer of a particle, it may be in a grafted, partially grafted or ungrafted form, preferably in a partially grafted or ungrafted form. At least a portion of the thermoplastic polymer (B1) may be grafted onto the polymer produced in the previous layer. If there are only two stages (SA1) and (SA2), which comprise polymers (A1) and (A2), respectively, a portion of the thermoplastic polymer (B1) may be grafted onto polymer (A2). In one embodiment, at least 50w%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, at least 98%, at least 99%, or 100% of the thermoplastic polymer (B1) is grafted onto the multistage polymer (MP1), in particular onto polymer (A2). In a preferred embodiment, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, at least 98%, at least 99%, or 100% by weight of polymer (B1) is not grafted on the multistage polymer (MP1), in particular on the polymer (A2). The grafting rate can be determined by using a solvent extraction of the polymer (B1) and performing a gravimetric test before and after the extraction to determine the amount of ungrafted. The amount of ungrafted corresponds to the amount (weight) of polymer (B1) dissolved by the solvent, and the amount of grafted corresponds to the amount (weight) of polymer (B1) that is not dissolved by the solvent and is still on the multistage polymer (MP1).
[0266] Thermoplastic polymer (B1) and polymer (A2) are not identical polymers, even though their compositions may be very close and their properties overlap. The essential difference is that polymer (A2) is always part of a multistage polymer (MP1).
[0267] The glass transition temperature Tg of the respective polymer can be estimated, for example, by dynamic methods such as thermomechanical analysis.
[0268] In order to obtain samples of the respective polymers (A1) and (A2), they can be prepared separately (and not by a multi-stage process) for separate estimation and easier measurement of the glass transition temperature Tg of the respective polymers of the respective stages. The polymer (B1) can be extracted for estimation and measurement of the glass transition temperature Tg.
[0269] The process for producing a multistage polymer (MP1) suitable for use as component (a) or components (a) and (b) of the curable composition according to the invention may comprise the following steps:
[0270] a) polymerizing the monomer or monomer mixture (A1m) by emulsion polymerization to obtain a layer comprising a polymer (A1) having a glass transition temperature of less than 10° C.; and
[0271] b) polymerizing the monomer or monomer mixture (A2m) by emulsion polymerization to obtain a layer comprising a polymer (A2) having a glass transition temperature of at least 60°C.
[0272] The monomer or monomer mixture (A1m) and the monomer or monomer mixture (A2m) are selected from monomers according to the composition of polymer (A1) and polymer (A2) as defined above. The characteristics of polymers (A1) and (A2) may be the same as defined above.
[0273] Preferably, step a) is carried out before step b). More preferably, if there are only two stages, step b) is carried out in the presence of the polymer (A1 ) obtained in step a).
[0274] The process for producing said multi-stage polymer may comprise further steps for further stages between steps a) and b).
[0275] The process for producing the multistage polymer may also comprise further steps for further stages before steps a) and b). The seed may be used to polymerize the monomer or monomer mixture (A1m) by emulsion polymerization to obtain a layer comprising a polymer (A1) having a glass transition temperature of less than 10° C. Preferably, the seed is a thermoplastic polymer having a glass transition temperature of at least 20° C.
[0276] The multistage polymer is obtainable as an aqueous dispersion of polymer particles. The solids content of the dispersion may be from 10 to 65% by weight, based on the weight of the dispersion.
[0277] As for the process for producing the thermoplastic polymer (B1), which may be component (b) of the curable composition of the present invention, such a process may comprise the step of polymerizing a monomer or a monomer mixture (B1m). The monomer or monomer mixture (B1m) is selected from monomers according to the composition of the polymer (B1) defined above.
[0278] The thermoplastic polymer (B1), which may be a homopolymer or a copolymer, may be prepared in a batch or semi-continuous process:
[0279] - for a batch process, the monomer or monomer mixture (B1m) can be introduced all at once just before or after the introduction of one of the initiator systems or a part of the initiator system;
[0280] For a semi-continuous process, the monomer or monomer mixture (B1m) can be added continuously in multiple additions or in parallel with the initiator addition (which can also be added multiple times or continuously) over a defined addition period (which can be in the range of 30 to 500 minutes).
[0281] The process for preparing the polymer composition comprising both a thermoplastic polymer (B1 ) (component (b)) and a multistage polymer (MP1 ) (component (a)) has two preferred embodiments.
[0282] In a first preferred embodiment of the process, the thermoplastic polymer (B1) is prepared by polymerizing one or more suitable monomers in the presence of the multistage polymer (MP1). Thus, the thermoplastic polymer (B1) is produced as a further stage of the multistage polymer (MP1).
[0283] In a second preferred embodiment of the process, the thermoplastic polymer (B1) is polymerized separately from the multistage polymer (MP1) and subsequently mixed or blended with the multistage polymer (MP1).
[0284] As far as the process for preparing a polymer composition comprising a thermoplastic polymer (B1) and a multistage polymer (MP1) according to a first preferred embodiment is concerned, it may comprise the following steps:
[0285] a) polymerizing a monomer or a monomer mixture (A1m) by emulsion polymerization to obtain a layer comprising a polymer (A1) having a glass transition temperature of less than 10° C.;
[0286] b) polymerizing the monomer or monomer mixture (A2m) by emulsion polymerization to obtain a layer comprising a polymer (A2) having a glass transition temperature of at least 60° C.; and
[0287] c) polymerizing the monomer or monomer mixture (B1m) by emulsion polymerization to obtain a layer comprising a thermoplastic polymer (B1 ) having a glass transition temperature of at least 30°C.
[0288] Preferably, step a) is carried out before step b). More preferably, step b) is carried out in the presence of the polymer (A1) obtained in step a).
[0289] Step c) can be carried out in such a way that at least a part or all of the thermoplastic polymer (B1) is not grafted to the polymer (A1) or the polymer (A2).
[0290] The respective monomers or monomer mixtures (A1m), (A2m), and (B1m) may be selected from monomers according to the composition of the polymers (A1), (A2), and (B1) as defined above. The characteristics of the polymers (A1), (A2), and (B1) may be the same as defined before.
[0291] Preferably, the process for the manufacture of a polymer composition comprising a thermoplastic polymer (B1) and a multistage polymer (MP1) comprises a step d) of recovering the polymer composition. "Recovering" means a partial or complete separation between an aqueous phase and a solid phase, wherein the latter phase comprises the polymer composition. More preferably, the recovery of the polymer composition is carried out by coagulation or by spray drying. Spray drying is a preferred method if the polymer (A1) having a glass transition temperature below 10°C comprises at least 50% by weight of polymerizable units derived from alkyl acrylates, based on the weight of polymer (A1), and stage (SA1) is the innermost layer of polymer particles having a multilayer structure. Coagulation is preferred if the polymer (A1) having a glass transition temperature below 10°C comprises at least 50% by weight of polymerizable units derived from isoprene or butadiene, based on the weight of polymer (A1), and stage (SA1) is the innermost layer of polymer particles having a multilayer structure.
[0292] The process for producing a polymer composition comprising a thermoplastic polymer (B1) and a multistage polymer (MP1) may optionally comprise a further step e) of drying the polymer composition. Preferably, the drying step e) is carried out if step d) of recovering the polymer composition is carried out by coagulation. Preferably, after the drying step e), the polymer composition comprises less than 3% by weight, more preferably less than 1.5% by weight, advantageously less than 1% by weight of water, based on the weight of the composition. The water content of the polymer composition can be measured using a thermal balance method. The drying of the polymer composition can be carried out in an oven, for example an oven in which the composition is heated at 50°C for 48 hours.
[0293] As regards the process for preparing a polymer composition comprising a thermoplastic polymer (B1) and a multistage polymer (MP1) according to the second preferred embodiment, such a process may comprise the following steps:
[0294] a) mixing a thermoplastic polymer (B1) and a multistage polymer (MP1); and
[0295] b) taking the mixture obtained in the previous step in the form of a polymer powder;
[0296] c) wherein the thermoplastic polymer (B1) and the multistage polymer (MP1) in step a) are in the form of a dispersion in an aqueous phase.
[0297] The amounts of aqueous dispersion of thermoplastic polymer (B1) and of aqueous dispersion of multistage polymer (MP1) can be chosen in such a way that the weight proportion of multistage polymer (MP1) in the obtained mixture is at least 5% by weight, preferably at least 10% by weight, more preferably at least 20% by weight and advantageously at least 50% by weight, based on the total amount of solids in the dispersion.
[0298] The amounts of aqueous dispersion of thermoplastic polymer (B1) and aqueous dispersion of multistage polymer (MP1) can be selected in such a way that the weight proportion of multistage polymer (MP1) in the obtained mixture is at most 99% by weight, preferably at most 95% by weight and more preferably at most 90% by weight, based on the total amount of solids in the dispersion.
[0299] The amounts of aqueous dispersion of thermoplastic polymer (B1) and of aqueous dispersion of multistage polymer (MP1) can be chosen in such a way that the weight proportion of multistage polymer (MP1) in the obtained mixture is between 5% and 99% by weight, preferably between 10% and 95% by weight and more preferably between 20% and 90% by weight, based on the total amount of solids in the dispersion.
[0300] Preferably, the recovery step b) of the process for the manufacture of a polymer composition comprising a thermoplastic polymer (B1) and a multistage polymer (MP1) comprises coagulation or spray drying. The process for the manufacture of a polymer composition comprising a thermoplastic polymer (B1) and a multistage polymer (MP1) may optionally comprise an additional step c) of drying the polymer composition. Preferably, after the drying step e), the polymer composition comprises less than 3% by weight, more preferably less than 1.5% by weight, advantageously less than 1% of water, based on the weight of the composition. The water content of the polymer composition can be measured using a thermal balance method. The drying of the polymer composition can be carried out in an oven, for example an oven in which the composition is heated at 50°C for 48 hours.
[0301] The process for producing a polymer composition comprising a thermoplastic polymer (B1) and a multistage polymer (MP1) preferably results in a polymer powder. The polymer powder may be in the form of particles. The polymer powder may comprise agglomerated polymer particles obtained by a multistage process and a thermoplastic polymer (B1).
[0302] Other components
[0303] The composition (P1) may further comprise an activator.
[0304] The activator may be selected to promote decomposition of the free radical initiator at room or ambient temperature to generate reactive free radical species so that curing of the curable composition is achieved without the need to heat or bake the curable composition.
[0305] In particular, the activator may be selected from: tertiary amines, metal salts or potassium salts, more particularly N,N-dimethyl-p-toluidine (DMPT), N,N-dihydroxyethyl-p-toluidine (DHEPT), N,N-diethyl-p-toluidine (DEPT), p-toluidine ethoxylate (PTE), iron, copper, cobalt, manganese, or vanadium salts, and mixtures thereof. Preferably, the activator is a tertiary amine or a cobalt salt.
[0306] In one embodiment, the composition (P1) comprises from 0.01 to 2%, in particular from 0.1 to 1%, more particularly from 0.2 to 0.5% by weight of activator, based on the weight of the composition (P1).
[0307] The composition (P1) may optionally contain one or more additives selected from the following: antioxidants / light stabilizers, light blockers / absorbers, polymerization inhibitors, foam inhibitors, flow or leveling agents, colorants, pigments, dispersants (wetting agents, surfactants), slip agents, chain transfer agents, thixotropic agents, matting agents, impact modifiers (other than the organic substances for multi-stage polymers and oligomeric polymerizations already mentioned), or other various additives.
[0308] In order to protect the curable composition from premature gelation or curing, especially in the presence of oxygen or other oxidants, one or more antioxidants may be included in the composition (P1). Any antioxidant known in the art may be used, including, for example, phenolic-based antioxidants, phosphorus-based antioxidants, quinone-type antioxidants, vitamin E, and combinations thereof.
[0309] Typically, one or more antioxidants may be included in composition (P1 ) in a total amount of up to 4 wt.-%, for example 0.05 to 2 wt.-%, based on the weight of composition (P1 ).
[0310] Advantageously, the composition (P1) of the present invention may be formulated to be solvent-free, i.e., to be free of any non-reactive volatile materials (materials having a boiling point of 150° C. or less at atmospheric pressure). For example, the curable composition of the present invention may contain little or no non-reactive solvent, for example, may contain less than 10%, or less than 5%, or less than 1%, or even 0% by weight of non-reactive solvent, based on the total weight of the curable composition. Such solvent-free or low-solvent compositions may be formulated using various components, including, for example, low-viscosity reactive diluents (such as mono(meth)acrylates), which may be selected so that the viscosity of the composition is low enough even in the absence of solvent so that it can be easily poured into a mold.
[0311] In one embodiment, the composition (P1) may comprise a mono(meth)acrylate obtained by adding a single (meth)acrylate group to an optionally alkoxylated monool or diol. The monool or diol may be aliphatic, cycloaliphatic (including one or more cycloaliphatic rings), or may contain one or more aromatic rings (as in the case of phenols or bisphenol A). Examples of suitable monools include, but are not limited to, linear, branched and cyclic C1-C36 monools (which may be primary, secondary or tertiary alcohols). For example, the monool may be a C1-C8 saturated aliphatic monool. In another embodiment, the monool may be a C10-C24 saturated aliphatic monool (e.g., lauryl alcohol, stearyl alcohol). Examples of suitable diols include ethylene glycol, 1,3-propylene glycol, and 1,3- and 1,4-butanediol.
[0312] In particular, the composition (P1) may comprise a mono(meth)acrylate selected from the group consisting of ethyl(meth)acrylate, n-butyl(meth)acrylate, isobutyl(meth)acrylate, tert-butyl(meth)acrylate, amyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, octyl(meth)acrylate / decyl(meth)acrylate, isodecyl(meth)acrylate, propylheptyl(meth)acrylate, dodecyl(meth)acrylate, tridecyl(meth)acrylate, stearyl(meth)acrylate, heptadecyl(meth)acrylate, cyclohexyl(meth)acrylate, benzyl(meth)acrylate, behenyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, (5-ethyl-1,3-dioxan-5-yl)methyl (meth)acrylate, (2,2-dimethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, isobornyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, methoxypolyethylene glycol mono(meth)acrylate, and alkoxylated (e.g. ethoxylated, propoxylated) derivatives thereof.
[0313] In one embodiment, the composition (P1) comprises 0 to 10% by weight, in particular 0 to 5%, more particularly 0 to 1%, even more particularly 0%, of a reactive diluent such as a mono(meth)acrylate, based on the weight of the composition (P1). In another embodiment, the composition (P1) comprises 1 to 30% by weight, in particular 5 to 25%, more particularly 10 to 20% by weight, based on the weight of the composition (P1).
[0314] Composition (P2)
[0315] The composition (P2) comprises a free radical initiator. The composition (P2) may comprise a mixture of free radical initiators.
[0316] In particular, the free radical initiator can be a peroxide, more particularly a hydroperoxide (ROOH), a dialkyl peroxide (ROOR) a peroxyacid (RC(O)-OOH), a peroxyester (RC(O)-OO-R'), a diacyl peroxide (RC(O)-OOC(O)-R'), a peroxyketal and mixtures thereof, R and R' being aliphatic, alicyclic, or aromatic groups.
[0317] Examples of suitable peroxides include: benzoyl peroxide, lauroyl peroxide, tert-butyl hydroperoxide, cyclohexanone peroxide, methyl ethyl peroxide, tert-butyl peroxyoctanoate, tert-butyl peroxybenzoate, dicumyl peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butyl peroxymaleate.
[0318] The free radical initiator may in particular be benzoyl peroxide.
[0319] In one embodiment, the curable composition of the present invention comprises 0.5 to 10, in particular 1 to 5 parts by weight of composition (P2) per 100 parts by weight of composition (P1).
[0320] Composition (P3)
[0321] The curable composition of the present invention may further comprise a composition (P3) comprising an inorganic filler. The composition (P3) may comprise a mixture of inorganic fillers.
[0322] In particular, the inorganic filler can be selected from marble, granite, quartz, diatomaceous earth, feldspar, mica, gypsum, glass microspheres, stone powder, limestone, ceramics, clay, sand, silicon dioxide, aluminum oxide, titanium dioxide, magnesium oxide, zirconium oxide, talc, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, zirconium hydroxide, calcium phosphate, calcium carbonate, barium sulfate, and mixtures thereof.
[0323] The composition (P3) may further optionally comprise a colorant or a mixture thereof. As used herein, the term "colorant" includes mineral or organic dyes, pigments, or any other substance other than the above-mentioned fillers that imparts color to the composition.
[0324] In one embodiment, the curable composition of the invention comprises 20 to 95%, in particular 50 to 90%, more particularly 60 to 80% by weight of composition (P3), based on the total weight of compositions (P1)+(P2)+(P3).
[0325] When composition P3 is present, the curable composition of the invention may be particularly suitable for obtaining artificial marble or artificial stone as described below.
[0326] Composition (P4)
[0327] The curable composition of the present invention may further comprise a composition (P4) comprising reinforcing fibers, in particular vegetable fibers, glass fibers, carbon fibers, polyester fibers, aramid fibers, and mixtures thereof.
[0328] In one embodiment, the curable composition of the invention comprises 20 to 95%, in particular 50 to 90%, more particularly 60 to 80% by weight of composition (P4), based on the total weight of compositions (P1)+(P2)+(P4).
[0329] When the composition P4 is present, the curable composition of the invention is particularly suitable for obtaining a composite as described below.
[0330] Polymerization process and products obtained therefrom
[0331] The present invention also relates to a process comprising polymerizing the curable composition according to the invention.
[0332] The polymerization may be carried out by mixing composition (P1) with composition (P2). Preferably, composition (P1) and composition (P2) are kept separate before polymerization occurs. Optional composition (P3) or (P4) may be present in the same phase as composition (P1) or composition (P2), preferably composition (P1).
[0333] The polymerization can be carried out at room temperature (20-25° C.), or accelerated by heating the composition. For example, the composition can be heated at a temperature of 60° C. or higher, in particular 90° C. or higher. The polymerization can be carried out for a time period of at least 20 minutes, in particular at least 30 minutes.
[0334] In one embodiment, the curable composition can be poured into a mold and polymerized. After the composition has been poured into the mold, it can be compacted by vacuum or vibration. The polymerization can be accelerated by heating as disclosed above. Once the composition has hardened, the article can be removed from the mold. After the article has been removed from the mold, it can be cut and polished.
[0335] The polymerization process of the present invention results in an article of manufacture.
[0336] The article of the invention is obtained by polymerizing the curable composition according to the invention.
[0337] The article of the present invention may be a molded article, a composite, an adhesive, a chemical anchoring system, a sealant, a dental filling, or an electrical insulation coating.
[0338] In one embodiment, the article may be a molded article obtained by polymerizing the curable composition of the present invention in a mold. In particular, the article of the present invention may be artificial marble or artificial stone.
[0339] As used herein, the term "artificial marble" refers to an article having the appearance of marble, comprising fillers dispersed in a polymer matrix. The artificial marble may be in the form of slabs or blocks.
[0340] As used herein, the term "artificial stone" refers to an article having the appearance of stone, comprising mineral fillers dispersed in a polymer matrix. The artificial stone may be in the form of a slab or a block.
[0341] The article of the present invention may be relatively thick. In particular, the article may exhibit a thickness of at least 0.2 cm, in particular at least 0.5 cm, more particularly at least 1 cm, even more particularly at least 2 cm. As used herein, the term "thickness" is intended to mean a dimension in a vertical direction relative to the plane of the article having the largest area.
[0342] Accordingly, the curable composition of the present invention can be used to prepare molded articles, composites, adhesives, chemical anchoring systems, sealants, dental fillings, or electrical insulating coatings; in particular artificial marble or artificial stone.
[0343] The artificial marble and artificial stone obtained according to the present invention have excellent aesthetic value, with patterns and chomaric shades not always seen in natural materials. Compared with conventional polyester-based artificial marble or artificial stone, the artificial marble or artificial stone of the present invention exhibits a glossy surface that does not tend to yellow even when aged in external conditions under UV radiation. Further, it exhibits excellent thermal resistance, excellent resistance to chemical agents, solvents, and dyes, and excellent mechanical resistance.
[0344] Application of additives (AD)
[0345] The invention also relates to the use of an additive in a curable composition for reducing cure shrinkage and reducing or preventing crack formation during polymerization of said composition.
[0346] The additive used according to the invention corresponds to the additive (AD) as defined above, said additive (AD) comprising:
[0347] a) a multistage polymer (MP1), said multistage polymer (MP1) comprising
[0348] a1) one grade (SA1) comprising a polymer (A1) having a glass transition temperature of less than 10°C; and
[0349] a2) one stage (SA2) comprising a polymer (A2) having a glass transition temperature of at least 60°C; and
[0350] b) A thermoplastic polymer (B1) having a glass transition temperature of at least 30°C.
[0351] There is no particular restriction on the curable composition in which the additive (AD) is used. In particular, the curable composition may comprise an ethylenically unsaturated compound, preferably a compound comprising a (meth)acrylate group, more preferably a compound comprising a methacrylate group, and optionally a free radical initiator. The ethylenically unsaturated compound may be a monomer (M1) as defined above, an oligomer (O1) as defined above, and a mixture thereof. The free radical initiator may be as defined above.
[0352] In one embodiment, the curable composition in which the additive (AD) is used comprises:
[0353] a) a first composition (P1'), said first composition (P1') comprising:
[0354] - a monomer (M1) comprising at least one (meth)acrylate group and at least one functional group selected from (meth)acrylate, hydroxyl, silane, ketone, and epoxy, preferably comprising 2 to 4, more preferably 2 or 3 (meth)acrylate groups, said monomer (M1) having a weight average molecular weight (Mw) of 100 to 420 g / mol, in particular 120 to 400 g / mol;
[0355] - an oligomer (O1) comprising at least 2 ethylenic unsaturations, preferably 2 to 10 ethylenic unsaturations, said oligomer (O1) having a weight average molecular weight (Mw) of 421 to 10 000 g / mol, in particular 450 to 3000 g / mol;
[0356] b) A second composition (P2'), said second composition (P2') comprising a free radical initiator.
[0357] Advantageously, the amount of additive (AD) used to reduce cure shrinkage and reduce or prevent crack formation during polymerization of the composition is low. In particular, the amount of additive (AD) used in the composition may be 1 to 15%, in particular 2 to 10%, more particularly 3 to 8%, even more particularly 4 to 6% by weight, based on the total weight of ethylenically unsaturated compounds (in particular, based on the total weight of monomers (M1) and oligomers (O1)).
[0358] The curable composition may include 15 to 80%, specifically 20 to 75%, more specifically 25 to 70% by weight of the monomer (M1), based on the weight of the curable composition.
[0359] The curable composition may include 15 to 80%, specifically 20 to 75%, more specifically 25 to 70% by weight of the oligomer (O1), based on the weight of the curable composition.
[0360] The curable composition of the present invention may further comprise a composition (P2) comprising a free radical initiator, as defined above.
[0361] The curable composition of the present invention may further comprise a composition (P3) comprising an inorganic filler, as defined above.
[0362] The curable composition of the present invention may further comprise a composition (P4) comprising reinforcing fibers, in particular vegetable fibers, glass fibers, carbon fibers, polyester fibers, aramid fibers, and mixtures thereof, as defined above.
[0363] The present invention is further described in detail in the following examples, which are provided for illustrative purposes only and are not intended to limit the scope of the present invention.
[0364] Example
[0365] Materials and methods
[0366] The following compounds were used in the examples:
[0367]
[0368] The following methods are used in the application:
[0369] Hybrid Approach
[0370] The additive (AD), when present, is dispersed in the monomer (M1) and oligomer (O1) by continuous mixing at 25°C for 30 to 45 minutes in a reactor with mechanical stirring at 2,000 to 2,500 rpm (optionally with an additional heating step at 50°C to improve dispersion of the additive).
[0371] Bulk polymerization method
[0372] The mixture of monomer (M1), oligomer (O1), and additive (AD) (when present) obtained by the mixing method is mixed in a reactor with 4 parts by weight of BP-40LV and 0.5 parts by weight 150PM are mixed together, and the weight parts are based on 100 weight parts of monomer (M1) and oligomer (O1). The mixture (120g) is poured into a metal cup with a diameter of 5cm and placed at room temperature to cure for 10 minutes. Once the reaction is complete, the solid material (which has a diameter of 5cm and a thickness of 3.5cm) is removed from the mold and cleaned with acetone.
[0373] Test tube polymerization method
[0374] The mixture of monomer (M1), oligomer (O1), and additive (AD) (when present) obtained by the mixing method is mixed in a reactor with 5 parts by weight of BP-40LV was mixed with 0.5 parts by weight of a tertiary amine based on 100 parts by weight of the monomer (M1) and the oligomer (O1). The mixture was poured into a glass test tube having a diameter of 1.5 cm and placed in a thermostatically controlled water bath at 25° C. The gelation time (Tgel, in minutes) and the exothermic peak (TEP, in ° C) were determined by measuring the temperature (in ° C) of the composition according to the time (in seconds) using a platinum temperature probe PT100 and a Yokogawa detector. Once the reaction was completed, a solid material (having a diameter of 1.5 cm and a thickness of 8 cm) was obtained.
[0375] Thin plate polymerization method
[0376] The mixture of the monomer (M1), oligomer (O1), and additive (AD) (when present) obtained by the mixing method is mixed in a reactor with 1 part by weight of P was mixed together, based on 100 parts by weight of monomer (M1) and oligomer (O1). The mixture (60 g) was poured between two glass plates (9 x 14 cm), which were separated by a 4 mm seal. The system was placed in an oven at 60° C. for 1 hour, then at 80° C. for 30 minutes, at 100° C. for 30 minutes, and at 120° C. for 30 minutes. Once the reaction was complete, the solid material (which had a width of 9 cm, a length of 14 cm, and a thickness of 4 mm) was removed from the mold and cleaned with acetone.
[0377] Weight average molecular weight
[0378] The weight average molecular weight is based on OCDE (1996), Test No.118: Determination of the Number-Average Molecular Weight and the Molecular Weight Distribution of Polymersusing Gel Permeation Chromatography, OECD Guidelines for the Testing ofChemicals, Section 1, OCDE, Paris, determined by size exclusion chromatography (SEC). The following conditions were used:
[0379] · 2 columns of mixed D (label 1110-6504) + 1 column (No. 1110-6520) + 1 column (No. 1110-6515), (7.8 mm x 300 mm), supplied by Agilent, the stationary phase is cross-linked polystyrene-divinylbenzene (PS-DVB) gel
[0380] · Flow rate of mobile phase (THF): 1 ml / min
[0381] Column temperature: 35°C
[0382] Detector: Refractive Index (RI)
[0383] Calibration: Polystyrene standards (Mw: 483.400, 215.000, 113.300, 51.150, 19.540, 10.110, 4.430, 2.930, 1.320, 575, 162 g / mol)
[0384] Glass transition temperature
[0385] The glass transition temperature (Tg) is measured by dynamic mechanical analysis (DMA). Before testing, the samples are stored at 23°C + / - 2°C and 50% + / - 10% relative humidity for 24 hours. DMA measures the change in the viscoelasticity of the sample as a function of the applied temperature, strain or deformation. The equipment continuously records the deformation of the sample during a controlled temperature change program while keeping the strain fixed. The results are obtained by plotting the elastic modulus (G', MPa), loss modulus (G", MPa) and tanδ as a function of temperature. Tg is the highest temperature value read in the tanδ curve, at which the derivative of tanδ is equal to 0.
[0386] The Tg of the different stages (SA1, SA2, B1, etc.) of the multistage polymer was measured using a "Rheometric Scientific RDAIII Dynamic Mechanical Analyzer" on samples (40 x 5 x 2 mm) in torque mode at a frequency of 1 Hz and a strain of 0.05%. The temperature was increased from -100°C to 200°C at a heating rate of 3°C / min.
[0387] The Tg of the oligomer (O1) and the polymerized product was measured using a "Rheometric Scientific RSA II Dynamic Mechanical Analyzer" on samples (80 x 10 x 4 mm, distance between the grips = 25 mm) in torque mode at a frequency of 1 Hz and a strain of 0.05%. The temperature was increased from -60°C to 200°C at a heating rate of 3°C / min.
[0388] Particle size analysis
[0389] The particle size of the primary particles after multi-stage polymerization was measured using a Zetasizer.
[0390] The particle size of the polymer powder after recovery was measured using a Malvern Mastersizer 3000 from MALVERN.
[0391] To estimate the weight average powder particle size, particle size distribution, and the proportion of fine particles, a Malvern Mastersizer 3000 apparatus with a 300 mm lens was used, measuring the range of 0,5-880 μm.
[0392] Viscosity
[0393] The viscosity was measured using a Brookfield viscometer (Fungilab α series) with a circulating water temperature regulation system to ensure a constant temperature of 25°C.
[0394] Three-point flexure test (breaking stress, breaking deflection, flexural modulus)
[0395] The three-point flexure test was carried out on a MTS1M / H traction bench at 23°C using standard ISO 178:2001. The speed was 2 mm / min and the distance between the two supporting pins was 6.4 cm (16 x thickness). The average thickness of the sample was 4 mm and the striking radius was 5 mm.
[0396] hardness
[0397] The hardness is determined using a Shore D hardness tester according to standard ISO 868: 1986. The measurement is carried out after 5 seconds of contact between the indenter and the sample.
[0398] Charpy impact test
[0399] CharpyThe impact test was carried out on a MTS Exceed E21 device according to standard ISO 179-1:2010. The measurements were carried out at 23°C, at 50% relative humidity, on unnotched specimens (80 x 10 x 4 mm), with impact in horizontal direction using a 2J pendulum.
[0400] Synthesis Example 1: Preparation of the Additive (AD) According to the Invention
[0401] The multistage polymer (MP1) was made in two stages according to the following synthesis:
[0402] First stage (SA1) - Polymerization of polymer (A1): A 20-liter autoclave was charged with: 116.5 parts of deionized water, 0.1 parts of an emulsifier (potassium salt of tallow fatty acid), 21.9 parts of 1,3-butadiene (BD), 0.1 parts of tert-dodecyl mercaptan, and 0.1 parts of p-menthane hydroperoxide as the initial kettle charge. The solution was heated to 43°C with stirring, at which time a redox-based catalyst solution (4.5 parts of water, 0.3 parts of sodium tetrapyrophosphate, 0.004 parts of ferrous sulfate, and 0.3 parts of dextrose) was charged, effectively initiating polymerization. Subsequently, the solution was further heated to 56°C and maintained at this temperature for a period of 3 hours. Three hours after the initiation of polymerization, the following were added continuously over 8 hours: a second monomer charge (77.8 parts BD, 0.2 parts tert-dodecyl mercaptan), half of the additional emulsifier and reducing agent charge (30.4 parts deionized water, 2.8 parts potassium salt of emulsifier tallow fatty acid, 0.5 parts dextrose), and additional initiator (0.8 parts p-menthane hydroperoxide). After the second monomer addition was completed, the remaining emulsifier and reducing agent charge, plus the initiator, were added continuously over an additional 5 hours. 13 hours after the initiation of polymerization, the solution was heated to 68° C. and allowed to react until 20 hours had passed since the initiation of polymerization, producing polybutadiene rubber latex R1 (A1). The resulting polybutadiene rubber latex R1 contained 38% solids and had a weight average particle size of about 160 nm.
[0403] Second stage (SA2) - Polymerization of polymer type (A2): A 3.9 liter reactor was charged with 75.0 parts (solids basis) of polybutadiene rubber latex R1, 37.6 parts of deionized water, and 0.1 parts of sodium formaldehyde sulfoxylate. The solution was agitated, purged with nitrogen, and heated to 77°C. When the solution reached 77°C, a mixture of 22.6 parts of methyl methacrylate, 1.4 parts of divinylbenzene, and 0.1 parts of tert-butyl hydroperoxide initiator was added continuously over 70 minutes, followed by an 80 minute hold period. 30 minutes after the start of the hold period, 0.1 parts of sodium formaldehyde sulfoxylate and 0.1 parts of tert-butyl hydroperoxide were added to the reactor. After the 80 minute hold period, the stabilized emulsion was added to the graft copolymer latex. The stabilized emulsion was prepared by mixing 3.2 parts of deionized water (based on the mass of the graft copolymer), 0.1 parts of oleic acid, 0.1 parts of potassium hydroxide, and 0.9 parts of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate. The resulting core-shell polymer (A1+A2) had a weight average particle size of about 180 nm. The final polymer (MP1) was then collected, the polymer composition was coagulated and dried to obtain a powder of core / shell-1.
[0404] According to a preferred embodiment, a thermoplastic polymer (B1) having a glass transition temperature of at least 30° C. is prepared as a further stage of the multistage polymer (MP1) according to the following synthesis:
[0405] Polymer (B1) was synthesized in a semi-continuous process: a reactor was charged with stirring: 10,000 g of core / shell-1 (A1+A2) (still as a dispersion in deionized water), 0.01 g of FeSO4 and 0.032 g of ethylenediaminetetraacetic acid, sodium salt (dissolved in 10 g of deionized water), 3.15 g of sodium formaldehyde sulfoxylate dissolved in 110 g of deionized water, and 21.33 g of emulsifier (potassium salt of tallow fatty acid) dissolved in 139.44 g of water, and the mixture was stirred until the added raw materials except the core-shell polymer were completely dissolved. Three vacuum-nitrogen purges were carried out successively, and the reactor was placed under a slight vacuum. Subsequently, the reactor was heated. At the same time, a monomer mixture containing 1066.7 g of methyl methacrylate and 10.67 g of n-octyl mercaptan was nitrogen degassed for 30 minutes. The reactor was heated at 63° C. and maintained at this temperature. Subsequently, using a pump, the monomer mixture was introduced into the reactor over 180 minutes. In parallel, a solution of 5.33 g of tert-butyl hydroperoxide (dissolved in 100 g of deionized water) was introduced (addition time was the same). 50 g and 20 g of water were used to rinse the pipeline. Subsequently, the reaction mixture was heated at a temperature of 80 ° C, and then the polymerization was completed after the addition of the monomer mixture was completed, for 60 minutes. The reactor was cooled to 30 ° C. The weight average molecular weight of polymer (B1) was Mw =28000g / mol.
[0406] The final polymer composition consisting of the stage polymer (MP1) and the polymer (B1) is then recovered, coagulated and dried to obtain a powder of core / shell-2.
[0407] Example 1: Curable composition
[0408] The curable composition is obtained by mixing monomer (M1), oligomer (O1), and optionally additive (AD) in the amounts given in the following table (% is % by weight, based on the total weight of monomer (M1), oligomer (O1), and additive (AD), phr. is parts by weight, based on 100 parts by weight of monomer (M1) and oligomer (O1)):
[0409]
[0410]
[0411] The components are mixed according to the mixing method, and the composition is cured using a bulk polymerization method, a thin sheet polymerization method, and a test tube polymerization method.
[0412] Example 2: Effect of additives (AD) on reducing cracking and curing shrinkage
[0413] Samples 2a, Comp 2, 3a, Comp 3, 4a, and Comp 4 of Example 1 were visually evaluated for the presence of cracks in the material obtained using the bulk polymerization method.
[0414]
[0415]
[0416] Samples containing a high amount of monomers, such as samples 4a and Comp 4, are more prone to crack formation during polymerization. For mixtures with a weight ratio between oligomer (O1) and monomer (M1) of 50 / 50 and 30 / 70, the addition of 5 phr. of the additive according to the invention (AD) reduces crack formation during polymerization. The introduction of the additive according to the invention (AD) also reduces the turbidity of the material.
[0417] The introduction of higher amounts of the additive according to the invention (AD) (10 phr. in samples 4b, 5b, and 6b) did not provide a further improvement on the crack reduction obtained with 5 phr. of the additive according to the invention (AD).
[0418] The reduction in crack formation achieved by 5 phr. of the additive according to the invention (AD) is confirmed by other difunctional monomers. Indeed, the materials obtained from samples 7a, 8a and 9a of Example 1 have fewer cracks or no cracks at all, and are less turbid than the same materials without any additive (Comp 7, Comp 8 and Comp 9, respectively). Sample 8a obtained from SR239 is particularly interesting since it appears transparent, has a reduced yellowness compared to Comp 8, and is crack-free.
[0419] Example 3: Effect of additives (AD) on thermal reactivity
[0420] For Samples 2a, Comp 2, 3a, Comp 3, 4a, and Comp 4 of Example 1, thermal reactivity was evaluated during the test tube polymerization process. Photos of each sample are shown in Figure 1 The gelation time (Tgel, in minutes) and the exothermic peak (TEP, in °C) of each sample are shown in the following table and Figure 2 middle.
[0421]
[0422] The addition of 5 phr. of the additive (AD) to the monomer (M1) and oligomer (O1) reduced the crack formation during polymerization without significantly changing the polymerization kinetics (slight differences are within the experimental error).
[0423] Example 4: Effect of additives (AD) on mechanical properties
[0424] For samples 2a, 2b, and Comp 2 of Example 1, the mechanical properties of the materials obtained using sheet polymerization are shown in the following table:
[0425]
[0426] The addition of 5 phr of additive (AD) to the mixture of monomer (M1) and oligomer (O1) did not significantly change the mechanical properties of the resulting material (the slight difference is within the experimental error). The addition of 10 phr of additive (AD) to the mixture of monomer (M1) and oligomer (O1) resulted in a decrease in the fracture stress, storage modulus E' in the rubbery region, and impact strength of the resulting material.
[0427] Example 5: Comparison with other additives
[0428] The presence of cracks in the materials obtained using the bulk polymerization method for samples 4a and Comp 4 of Example 1 (containing the additive (AD) according to the invention) was compared with materials obtained using other additives (not according to the invention). The photographs of the samples are shown in Figure 3 middle.
[0429]
[0430]
[0431] Only sample 4a according to the invention produced a transparent and crack-free polymerized article.
Claims
1. A curable composition comprising: i) a composition P1 comprising: - a monomer M1, the monomer M1 comprising at least two (meth)acrylate groups, or at least one (meth)acrylate group and at least one functional group selected from hydroxyl, silane, ketone, and epoxy, the monomer M1 having a weight average molecular weight (Mw) of 100 to 420 g / mol; - oligomer O1, said oligomer O1 comprising at least 2 ethylenic unsaturations, said oligomer O1 having a weight average molecular weight (Mw) of 421 to 10000 g / mol; - an additive AD, said additive AD comprising: a) a multistage polymer MP1, said multistage polymer MP1 comprising a1) a grade SA1 comprising a polymer A1 having a glass transition temperature of less than 10° C.; and a2) one grade SA2 comprising a polymer A2 having a glass transition temperature of at least 60° C.; and b) a thermoplastic polymer B1 having a glass transition temperature of at least 30° C.; and ii) a composition P2 comprising a free radical initiator, in The composition P1 comprises from 15 to 80% by weight of monomer M1, based on the weight of the composition P1, The composition P1 comprises from 15 to 80% by weight of oligomer O1, based on the weight of the composition P1, The composition P1 comprises from 1 to 8% by weight of additives AD, based on the weight of the composition P1, and The curable composition comprises 0.5 to 10 parts by weight of composition P2 for 100 parts by weight of composition P1. 2 . The curable composition according to claim 1 , characterized in that the monomer M1 has a weight average molecular weight (Mw) of 120 to 400 g / mol. 3 . The curable composition according to claim 1 , wherein the oligomer O1 comprises 2 to 10 ethylenic unsaturations. 4 . 4 . The curable composition according to claim 1 , wherein the oligomer O1 has a weight average molecular weight (Mw) of 450 to 3000 g / mol.
5. The curable composition according to claim 1 or 2, characterized in that the monomer M1 comprises: - at least 2 (meth)acrylate groups; or - at least one (meth)acrylate group and at least one hydroxyl group.
6. The curable composition according to claim 5, characterized in that the monomer M1 comprises: - 2 to 4 (meth)acrylate groups; or - at least one (meth)acrylate group and at least one hydroxyl group.
7. The curable composition according to claim 5, characterized in that the monomer M1 comprises: - 2 or 3 (meth)acrylate groups; or - at least one (meth)acrylate group and at least one hydroxyl group.
8. The curable composition according to claim 1 or 2, characterized in that the monomer M1 is represented by the following formula (I): in R1 is H or methyl; L is a (x+y)-valent linker; M is a functional group selected from hydroxyl, silane, ketone, and epoxy; x is 0, 1, 2, or 3; y is 1, 2, 3, 4, 5, or 6; The condition is that x+y≥2.
9. A curable composition according to claim 8, characterised in that R1 is methyl.
10. The curable composition according to claim 8, characterized in that L is selected from alkylene, alkoxylated alkylene, polyoxyalkylene, or polyester.
11. The curable composition according to claim 1 or 2, characterized in that the monomer M1 is represented by the following formula (II): in Each R1 is independently H or methyl; L is a divalent linker selected from alkylene, alkoxylated alkylene, polyoxyalkylene, or polyester; x is 0 or 1; y is 1 or 2; The condition is, x+y=2.
12. Curable composition according to claim 11, characterized in that R1 is methyl.
13. The curable composition according to claim 11, characterized in that L is a divalent linker selected from one of the following formulae: -(CR3R’3) a -,-[(CR4R’4) b -O] c -(CR4R’4) b -, -[(CR5R'5) d -THE] e -(CR6R'6) f -[O-(CR5R'5) d’ ] e’ -[(CR7R'7) g -C(=O)O] h -[(CR8R'8) i -O] j -(CR8R'8) i -[OC(=O)-(CR7R'7) g’ ] h’ -;in R3, R'3, R4, R'4, R5, R'5, R6, R'6, R7, R'7, R8, and R'8 are independently H or alkyl; a and f are independently 2 to 20; b, d, d', and i are independently 2 to 6; c is 1 to 20; e and e' are independently 0 to 20, provided that at least one of e and e' is not 0; g and g' are independently 3 to 12; h and h' are independently 0 to 20, provided that at least one of h and h' is not 0; j is 0 to 20.
14. The curable composition according to claim 13, characterized in that R3, R'3, R4, R'4, R5, R'5, R6, R'6, R7, R'7, R8, and R'8 are independently H or methyl.
15. The curable composition according to claim 13, characterized in that a and f are independently 2 to 10.
16. The curable composition according to claim 13, characterized in that b, d, d', and i are independently 2 to 4.
17. The curable composition according to claim 13, characterized in that c is from 1 to 10.
18. The curable composition according to claim 13, characterized in that e and e' are independently from 0 to 10, with the proviso that at least one of e and e' is not zero.
19. The curable composition according to claim 13, characterized in that g and g' are independently 5.
20. The curable composition according to claim 13, characterized in that h and h' are independently from 0 to 10, with the proviso that at least one of h and h' is not zero.
21. The curable composition according to claim 13, characterized in that j is from 0 to 10.
22. A curable composition according to claim 11, characterized in that L is a divalent linker selected from the group consisting of: alkylene; alkoxylated derivatives of the aforementioned alkylene; residues of di-, tri-, tetra- or polyoxyalkylene without OH groups; and esterified derivatives of the aforementioned oxyalkylene.
23. Curable composition according to claim 22, characterized in that the alkylene group is selected from ethylene, 1,3-propanediyl, 1,3-butanediyl, 1,4-butanediyl, 1,5-pentanediyl, 1,6-hexanediyl, 1,10-decanediyl, 3-methyl-1,5-pentanediyl, 2,2-dimethyl-1,3-propanediyl.
24. Curable composition according to claim 22, characterized in that the alkoxylated derivatives of the aforementioned alkylene groups are ethoxylated and / or propoxylated derivatives of the aforementioned alkylene groups.
25. Curable composition according to claim 22, characterized in that the residue of the di-, tri-, tetra- or polyoxyalkylene group without OH groups is selected from di-, tri- or tetraethylene glycol, di-, tri- or tetrapropylene glycol, di-, tri- or tetrabutylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, poly(ethylene glycol-co-propylene glycol).
26. The curable composition according to claim 22, characterized in that the esterified derivative of the aforementioned oxyalkylene group is a derivative of the aforementioned oxyalkylene group esterified by ring-opening polymerization of a lactone.
27. A curable composition according to claim 1 or 2, characterized in that the monomer M1 is represented by the following formula (III): in Each R1 is independently H or methyl; L is a tri- or tetravalent linker selected from alkylene, alkoxylated alkylene, polyoxyalkylene, or polyester; x is 0, 1, 2, or 3; y is 1, 2, 3, or 4; The condition is that x+y=3 or 4.
28. A curable composition according to claim 27, characterised in that R1 is methyl.
29. The curable composition according to claim 27, characterized in that L is a trivalent linker corresponding to formula (IV), or a tetravalent linker corresponding to formula (V) or (VI): in R p and R' p are independently H or methyl; R 10 is selected from H, alkyl, and alkoxy; n, n', and n" are independently 0 to 2, provided that at least two of n, n', and n" are not 0; o, o', and o" are independently 2 to 4; p, p', and p" are independently 0 to 10; in R q and R' q are independently H or methyl; q, q', q", and q'" are independently 0 to 2, provided that at least 3 of q, q', q", and q'" are not 0, r, r', r", and r'" are independently 2 to 4; s, s', s", and s'" are independently 0 to 10; in R r and R' r are independently H or methyl; t, t', t", and t'" are independently 2 to 4; u, u', u", and u'" are independently 0 to 10.
30. A curable composition according to claim 29, characterised in that, in formula (IV), R 10 It is an alkyl group.
31. The curable composition according to claim 29, characterized in that, in formula (IV), n, n', and n" are all 1 or n is 0 and n' and n" are 1.
32. A curable composition according to claim 29, characterized in that, in formula (IV), o, o', and o" are independently 2.
33. The curable composition according to claim 29, characterized in that, in formula (IV), p, p', and p" are independently 0 to 6.
34. The curable composition according to claim 29, characterized in that, in formula (V), q, q', q", and q'" are all 1.
35. The curable composition according to claim 29, characterized in that, in formula (V), r, r', r", and r'" are independently 2.
36. The curable composition according to claim 29, characterized in that, in formula (V), s, s', s", and s'" are independently 1 to 6.
37. The curable composition according to claim 29, characterized in that, in formula (VI), t, t', t", and t'" are independently 2.
38. The curable composition according to claim 29, characterized in that, in formula (VI), u, u', u", and u'" are independently 1 to 6.
39. Curable composition according to claim 1 or 2, characterised in that the composition P1 comprises 20 to 75% by weight of monomer M1, based on the weight of the composition P1.
40. Curable composition according to claim 1 or 2, characterized in that the composition P1 comprises 25 to 70% by weight of monomer M1, based on the weight of the composition P1.
41. A curable composition according to claim 1 or 2, characterized in that the oligomer O1 is selected from: epoxy (meth)acrylates, urethane (meth)acrylates, polyester (meth)acrylates, polyether (meth)acrylates, (meth)acrylated poly (meth)acrylates, unsaturated polyesters, polybutadiene, vinyl ethers, amine-modified or thiol-modified derivatives of the aforementioned oligomers, and mixtures thereof.
42. A curable composition according to claim 41, characterised in that the oligomer O1 is selected from epoxy (meth)acrylates, urethane (meth)acrylates, polyester (meth)acrylates, polyether (meth)acrylates, and mixtures thereof.
43. A curable composition according to claim 41, characterised in that the oligomer O1 is selected from epoxy methacrylates, urethane methacrylates, polyester methacrylates, polyether methacrylates, and mixtures thereof.
44. Curable composition according to claim 1 or 2, characterized in that the composition P1 comprises 20 to 75% by weight of oligomer O1, based on the weight of the composition P1.
45. Curable composition according to claim 1 or 2, characterized in that the composition P1 comprises 25 to 70% by weight of oligomer O1, based on the weight of the composition P1.
46. A curable composition according to claim 1 or 2, characterized in that the additive AD contains 4 to 40%, 5 to 35%, 6 to 30%, 7 to 28%, 8 to 25%, 9% to 22%, or 10% to 20% by weight of thermoplastic polymer B1, based on the total weight of multistage polymer MP1 and thermoplastic polymer B1.
47. Curable composition according to claim 1 or 2, characterized in that the composition P1 comprises 2.5 to 8% by weight of additive AD, based on the weight of the composition P1.
48. Curable composition according to claim 47, characterised in that the composition P1 comprises 3.5 to 6% by weight of additive AD, based on the weight of the composition P1.
49. A curable composition according to claim 1 or 2, characterised in that the composition P2 comprises a peroxide as free radical initiator.
50. A curable composition according to claim 49, characterised in that the peroxide is selected from the group consisting of hydroperoxides (ROOH), dialkyl peroxides (ROOR), peroxyacids (RC(O)-OOH), peroxyesters (RC(O)-OO-R'), diacyl peroxides (RC(O)-OOC(O)-R'), peroxyketals, and mixtures thereof, R and R' being aliphatic, cycloaliphatic, or aromatic groups.
51. A curable composition according to claim 1 or 2, characterised in that the composition P1 further comprises an activator.
52. Curable composition according to claim 51, characterized in that the activator is selected from: tertiary amines, metal salts.
53. A curable composition according to claim 52, characterised in that the metal salt is a potassium salt.
54. A curable composition according to claim 51, characterized in that the activator is selected from: N,N-dimethyl-p-toluidine (DMPT), N,N-dihydroxyethyl-p-toluidine (DHEPT), N,N-diethyl-p-toluidine (DEPT), p-toluidine ethoxylate (PTE), iron, copper, cobalt, manganese, or vanadium salts, and mixtures thereof.
55. A curable composition according to claim 51, characterised in that the activator is a tertiary amine or a cobalt salt.
56. Curable composition according to claim 1 or 2, characterized in that it comprises 1 to 5 parts by weight of composition P2 per 100 parts by weight of composition P1.
57. A curable composition according to claim 1 or 2, characterised in that it further comprises a composition P3 comprising an inorganic filler.
58. A curable composition according to claim 57, characterised in that the composition P3 comprises an inorganic filler selected from the group consisting of marble, granite, quartz, diatomaceous earth, feldspar, mica, gypsum, glass microspheres, stone powder, limestone, ceramics, clay, sand, silicon dioxide, aluminum oxide, titanium dioxide, magnesium oxide, zirconium oxide, talc, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, zirconium hydroxide, calcium phosphate, calcium carbonate, barium sulfate and mixtures thereof.
59. Curable composition according to claim 57, characterized in that it comprises 20 to 95% by weight of composition P3, based on the total weight of composition P1+P2+P3.
60. Curable composition according to claim 59, characterized in that it comprises 50 to 90% by weight of composition P3, based on the total weight of composition P1+P2+P3.
61. Curable composition according to claim 59, characterized in that it comprises 60 to 80% by weight of composition P3, based on the total weight of composition P1+P2+P3.
62. A curable composition according to claim 1 or 2, characterised in that it further comprises a composition P4 comprising reinforcing fibres.
63. A curable composition according to claim 62, characterised in that the reinforcing fibres are selected from the group consisting of vegetable fibres, glass fibres, carbon fibres, polyester fibres, aramid fibres, and mixtures thereof.
64. Curable composition according to claim 62, characterized in that it comprises 20 to 95% by weight of composition P4, based on the total weight of composition P1+P2+P4.
65. Curable composition according to claim 64, characterized in that it comprises 50 to 90% by weight of composition P4, based on the total weight of composition P1+P2+P4.
66. Curable composition according to claim 64, characterized in that it comprises 60 to 80% by weight of composition P4, based on the total weight of composition P1+P2+P4.
67. A process comprising polymerizing a curable composition as claimed in any one of claims 1 to 66.
68. An article obtained by polymerizing a curable composition as claimed in any one of claims 1 to 66.
69. Article according to claim 68, characterized in that it exhibits a thickness of at least 0.2 cm.
70. Article according to claim 69, characterized in that it exhibits a thickness of at least 0.5 cm.
71. Article according to claim 69, characterized in that it exhibits a thickness of at least 1 cm.
72. Article according to claim 69, characterized in that it exhibits a thickness of at least 2 cm.
73. The article according to any one of claims 68 to 72, characterized in that it is a molded article, a composite, an adhesive, a chemical anchoring system, a sealant, a dental filling, or an electrical insulation coating.
74. The article according to claim 73, characterized in that the article is artificial marble.
75. The article according to claim 73, characterized in that the article is artificial stone.
76. Use of a curable composition as claimed in any one of claims 1 to 66 for the preparation of a moulding, a composite, an adhesive, a chemical anchoring system, a sealant, a dental filling or an electrical insulating coating.
77. Use of a curable composition as claimed in any one of claims 1 to 66 for preparing artificial marble.
78. Use of a curable composition as claimed in any one of claims 1 to 66 for the preparation of artificial stone.
79. Use of an additive in a curable composition as claimed in claim 1 for reducing cure shrinkage and reducing or preventing crack formation during polymerization of the composition, the additive being additive AD, the additive AD comprising: a) a multistage polymer MP1, said multistage polymer MP1 comprising a1) a grade SA1 comprising a polymer A1 having a glass transition temperature of less than 10° C.; and a2) one grade SA2 comprising a polymer A2 having a glass transition temperature of at least 60° C.; and b) A thermoplastic polymer B1 having a glass transition temperature of at least 30°C.
Citation Information
Patent Citations
Silicon-containing (meth)acrylate compounds
CN104271623A
(METH) acrylic adhesive composition, its method of preparation and its use
WO2019012088A1